QSRR-Based RP-HPLC Method Development for Antiviral Drug Analysis: Machine Learning, Design of Experiments, and Sustainable Analytical Strategies—A Review - Pawan Kumar Goswami; Sonakshi Antal; Arvind Kumar Patel (Journal of Pharmaceutical Innovation, 2027)

3D Cerium Doped In2S3 Immobilised Hydrogel for Efficient Photocatalytic Sulphamethoxazole Degradation via PMS Activation and H2O2 Production- Mechanistic Insights and Applications - Hritankhi Tripathy; Abhijeet Sahoo; Arvind Kumar (Water Conservation Science and Engineering, 2026)

Therapeutic potential of a novel spirocyclic molecule in a murine model of peripheral nerve injury mediated via anti-inflammatory and neuroprotective properties - Soumya Ghosh; Papia Basuthakur; Vincy Vijay; Joachyutharayalu Oja; Ramesh Samineni; Debiprasad Sinha; Pratistha Wadnerkar; Srihari Pabbaraja; Goverdhan Mehta; Arvind Kumar; Sumana Chakravarty (Molecular Biology Reports, 2026)

Regulation of mitochondrial fission by Drp1 in cardiomyopathy: possible mechanisms linking cellular processes to cell death - Nandini Dubey; Pranav Panchbhai; Gauri Chaturvedi; Satnam Singh; Ahsas Goyal; Neeraj Parakh; Rajiv Narang; Sudhir Kumar Arava; Arvind Kumar; Mayank Yadav; Harlokesh Narayan Yadav (Molecular Biology Reports, 2026)

Host-mediated variation in insect biology, feeding efficiency and defensive phytochemicals underlying resistance of poplar clones to Clostera cupreata (Butler, 1881) - Arvind Kumar; Jitendra Kumar; Tanmaya Kumar Bhoi; Deepak Kumar Mahanta (Phytoparasitica, 2026)

Novel application of a Fenton-like CWPO system using iron-functionalized lignocellulosic biochar for landfill leachate treatment - Tina Kenneth; Riona Indhur; Arvind Kumar; Moeti Kgware; Sheena Kumari (Journal of Water Process Engineering, 2026)

Dual-functional SnS2-β-amylase nanobiocatalyst from Ficus benghalensis: Immobilization-induced antioxidant synergy for sustainable starch hydrolysis - Anikesh Kumar; Ashish Jyoti Borah; Shailly Saini; Anchal Srivastava; Arvind M. Kayastha (Food Bioscience, 2026)

Thermal behaviour and energy performance of driven precast energy piles in Norwegian quick clay: a full-scale field study - Arvind Kumar Tiwari; Habibollah Sadeghi; Rao Martand Singh (Energy and Buildings, 2026)

Rainfall and Its Stable Isotopic Composition Variability over Nagpur, India: Possible Controlling Processes During Southwest Monsoon 2022 - P. Kiran Kumar; Arvind Singh; M. G. Yadava; C. S. Sindhuja (Pure and Applied Geophysics, 2026)

Modeling the impact of adiponectin on tumor-immune dynamics: Stability, bifurcations, and optimal control - Himanshu Jain; Ken Tye Yong; Nishant Namdev; Madhurima Deb; Arun Jaiswal; Arvind Kumar Sinha (Mathematical Biosciences, 2026)

Impacts of cooperative hunting and Allee effect on the dynamics of a three-species system with sexually reproducing top predators - Sayan Mandal; Pankaj Kumar Tiwari; Ranjit Kumar Upadhyay; Arvind Kumar Misra (Mathematical Biosciences, 2026)

Impact of sedimentary processes on tectonic inferences for a Precambrian sedimentary basin using elemental geochemistry: A case study from the Papaghni sub-basin, Cuddapah Basin, India - Faizan Ahmad Khan; Gundiga P. Gurumurthy; Kumail Ahmad; Arvind Kumar Singh; Mahboob Alam; Mohammad Arif; Anupam Sharma (Geochemistry, 2026)

Necessity to upgrade existing plant tolerance indices for sustainable urban greenbelt development - Durga Prasad Tripathi; Arvind Kumar Nema (Environmental Sustainability, 2026)

ARF Gene Family: Expression Dynamics, Signalling, and Importance in Seed Development - Kumari Arpita; Sandhya Sharma; Anshika Tyagi; Arvind Yadav; Sandeep Kumar; Rupesh Deshmukh; Robert M Stupar; Kishor Gaikwad (Journal of Plant Growth Regulation, 2026)

Rhizosphere microbial population and their plant growth-promoting functionality are influenced by soil sodicity and crop diversity - Pooja Verma; Priyanka Chandra; Arvind Kumar Rai; Nirmalendu Basak; Kailash Prajapat; Ram Kishor Fagodiya; Parul Sundha; Baljeet Singh Saharan; Rajender Kumar Yadav (Soil and Tillage Research, 2026)

Natural Ingredients-based pyrotechnic aerosol forming composite for quick fire extinguishment - Braham Prakash; Amit Saxena; Yogesh Kumar Tyagi; I.P. Singh; Arvind Kumar (Process Safety and Environmental Protection, 2026)

Preparation, characterization, and in-vivo evaluation of a polyherbal gel for anti-arthritic potential using medicinal plant extracts - Supriya Garg; Vaishali; Bhuwanendra Singh; Piyush Kumar Singhal; Arvind Kumar; Mahima (Next Research, 2026)

Mixed organic acid–mediated activation of sodium percarbonate on kaolinite toward enhanced tetracycline degradation: Mechanistic elucidation and toxicological assessments - Khwairakpam Bidya Devi; Akash Balakrishnan; Arvind Kumar; Mahendra Chinthala; Natarajan Rajamohan; Tejraj M. Aminabhavi (Chemical Engineering Journal, 2026)

Visible-Light-Driven BiVO₄-Alginate Hydrogel: An Ecofriendly High-Performance Photocatalyst for Tetracycline Hydrochloride Removal via Peroxymonosulphate Activation - Hritankhi Tripathy; Tvisha Rachel Binoy; Shiv Charan Prajapati; Arvind Kumar (Water, Air, & Soil Pollution, 2026)

Effect of Graded Molybdenum Application on Soil Molybdenum Pools, Critical Threshold and Cauliflower Productivity in an Acid Alfisols - Himshikha; Nagender Pal Butail; Anjali; Praveen Thakur; Arvind K. Shukla; Sanjib K. Behera; Shilpa Kumari; Shweta Sharma; Priyanka; Mansi Bahman; Mohit Kashyap; Aarush Lal; et al. (Journal of Soil Science and Plant Nutrition, 2026)

A Robust Hybrid Deep Learning Model for GHI Forecasting Incorporating EEMD, CSA Optimization, and Transformer–GRU Networks - Girijapati Sharma; Subhash Chandra; Arvind Kumar Yadav (Pure and Applied Geophysics, 2026)

Pharmacognostical standardization and in-silico anticancer study of selected medicinal plants obtained polyherbal extract - Pratiksha Tyagi; Bhuwanendra Singh; Mahima; Piyush Kumar Singhal; Arvind Kumar; Vaishali (Next Research, 2026)

Phytochemical profiling of different stem extracts of Cissus quadrangularis Linn. as a natural source of resveratrol through TLC, HPTLC & NMR spectroscopy - Arvind Kumar; Tanuja; Vinay Bhushan Kumar (Next Research, 2026)

Oxalic acid–assisted, metal-free light-driven activation of sodium percarbonate on kaolinite for tetracycline degradation in water: Kinetic, mechanistic, and toxicological insights - Khwairakpam Bidya Devi; Akash Balakrishnan; Mary Nancy Flora; Arvind Kumar; Mahendra Chinthala; Natarajan Rajamohan; Sami Rtimi (Journal of Environmental Management, 2026)

Habitat suitability modelling and citizen science data to strengthen river basin-scale conservation planning for threatened aquatic avifauna - Arvind Kumar Dwivedi; Kritish De (Ecohydrology & Hydrobiology, 2026)

Prediction of Aerosol Optical Depth Using a Support Vector Machine Model in the Coal Mining Regions of Assam - Nishant Kumar; Kirti Soni; Kulwinder Singh Parmar; Pranalee Thorat; Dipankar Saha; Arvind Kumar Jha; Anikender Kumar; Vijay Kumar Soni (Journal of the Indian Society of Remote Sensing, 2026)

Intercomparison and Validation of SODAR and ERA5 Measured Atmospheric Boundary Layer Height Over Delhi - Nishant Kumar; Anjali S. Nair; Avni Tiwari; Kirti Soni; V. K. Soni; Anikender Kumar; Arvind Jha; Dharmendra Gupta (Journal of the Indian Society of Remote Sensing, 2026)

Fuzzy-Clustering Driven Soil Nutrients Management Zone Delineation in Mandarin (Citrus reticulata Blanco) Growing Areas of Malwa Plateau Region of India - Seema Bhardwaj; Sanjib Kumar Behera; Rahul Mishra; Sanjay Kumar Sharma; Sudhir Kumar Trivedi; Vimal Shukla; Akanksha Sikarwar; Arvind Kumar Shukla (Journal of Soil Science and Plant Nutrition, 2026)

Ideotype-based Selection of Superior Rice Genotypes using the MGIDI Framework for Germination, Agronomic Performance, Blast Resistance, Drought Tolerance, and Nutritional Quality - Atefeh Sabouri; Zahra Esmaeilpour; Tayebeh Raiesi; Reza Afshari; Fatemeh Alinezhad; Haniyeh Babaei-Raouf; Elham Nasiri; Masoud Esfahani; Sedigheh Mousanejad; Akbar Forghani; Arvind Kumar (Journal of Soil Science and Plant Nutrition, 2026)

Synergistic photodynamic inactivation of Escherichia coli using curcumin-trehalose photosensitizer under blue visible light on fresh-cut dragon fruit (Hylocereus undatus) - Jawaharlal Nehru Garimella; Hritankhi Tripathy; Arvind Kumar; Rama Chandra Pradhan (Postharvest Biology and Technology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Trade-offs and synergies in nitrogen management for fodder sorghum: enhancing yield, energy efficiency, and carbon budgeting - Mohd Arif; R. Pourouchottamane; Ravindra Kumar; Arvind Kumar; Mohammad Hasanain; B. Rai; M.K. Singh; A.K. Dixit; Rakesh Kumar; Vijay Singh Meena; Raghavendra Singh; Sunita Kumari Meena; et al. (Biomass and Bioenergy, 2026)

Synthetic approach for the oxidative depolymerization of biomass-derived lignin to vanillin, vanillic acid, and acetovanillone compounds - Rohit Bains; Mahender Kumar; Arvind Singh Chauhan; Ajay Kumar; Pralay Das (Bioresource Technology Reports, 2026)

Vegetation loss and climate-driven fragmentation in the Himalayan alpine ecosystem: an AI/ML-based LULC and carbon stock analysis - Akash Kashyap; Vijendra Kumar Pandey; Dipankar Bera; Deepanshu Parashar; Ashwani Kumar; Arvind Pandey; Sajid Ullah; Wafa Saleh Alkhuraiji; Mohamed Zhran (Theoretical and Applied Climatology, 2026)

An Integrative Morphometric Approach to Resolving Taxonomic Ambiguity in Sympatric Mullet Species (Mugilidae) from Attangarai Vaigai River Estuary, Tamil Nadu, India - Kritish De; Arvind Kumar Dwivedi (Thalassas: An International Journal of Marine Sciences, 2026)

Temperature Dependency of Grout Efficiency in Improving Mechanical Response of Jointed Sandstone Under Different Loading Conditions - Gaurav Kumar Mathur; Arvind Kumar Jha; Gaurav Tiwari (Rock Mechanics and Rock Engineering, 2026)

Optimizing Zinc Biofortification in Wheat With 4R Nutrient Stewardship Approach for Sustainable Micronutrient Management - Arvind Kumar Yadav; Malu Ram Yadav; Milan Kumar Lal; Ajay Kumar; Dinesh Kumar (Journal of Soil Science and Plant Nutrition, 2026)

Augmenting the Elemental Sulphur–based Formulation with Pseudomonas Chloritidismutans Strain WH2 for Improved Sodic Soil Reclamation and Crop Performance - Arvind Kumar Rai; Nirmalendu Basak; Priyanka Chandra; Parul Sundha; Harshpreet Kaur; Sandeep Bedwal; Subedar Patel; Sanjay Kumar; Rameshwar Lal Meena; Parbodh Chander Sharma; Rajender Kumar Yadav (Journal of Soil Science and Plant Nutrition, 2026)

Integrated morpho-molecular diversity and population structure analysis of Indian mustard (Brassica juncea L.) germplasm for strategic breeding in the Northern Gangetic plains - Aachal Futane; Sahil G. Shamkuwar; Shivangi Saha; Rohit Kumar Verma; Pooja Yadav; Arvind Patel; Arun Balasubramaniam; Srikanth Urati; P. Vijai; Kartikeya Srivastava (Genetic Resources and Crop Evolution, 2026)

Correction: Tandem mass spectrometry based study on the dissipation behaviour, dietary risk assessment and decontamination of chlorfenapyr, fenvalerate, and tolfenpyrad residues in broccoli - Sapna Katna; Preeti Bansal; Ajay Sharma; Tanuja Banshtu; Nisha Devi; Arvind Kumar; Shubhra Singh; Sakshi Sharma; Ankur Tomar (Environmental Geochemistry and Health, 2026)

Delineation of Soil Nutrient Management Zone for Site-Specific Sulphur and Micronutrient Management: A Case Study of Jhansi Bundelkhand Region of India - Rahul Mishra; Sanjib Kumar Behera; Arvind Kumar Shukla; Vimal Shukla (Agricultural Research, 2026)

Interannual variability in seed germination of Plantago asiatica and its implications for cultivation - Arvind Bhatt; Harsh Kumar Chauhan; Mohammed Dadach (Vegetos, 2026)

Biogenicity of amorphous carbonaceous matter in the hemispheroidal microbialites of Paleoproterozoic Bajna Dolomite - Arif Husain Ansari; Yogmaya Shukla; Gaurav Kumar Singh; Arvind Kumar Singh; Archana Sonker; Mohammad Arif Ansari (Journal of Earth System Science, 2026)

Flood Hazard and Risk Assessment Using Satellite-Derived Flood Events (2001–2025) and Socioeconomic Data in Bihar - Randhir Kumar; Arvind Chandra Pandey; Kiran Jalem; Bikash Ranjan Parida (Journal of the Indian Society of Remote Sensing, 2026)

Integrating nature-based solutions and governance for air pollution mitigation in Delhi: the Delhi Great Green Wall framework - Arun Kumar; Jayanthi Jaganathan; Balkrishna Sopan Bhople; Arvind Kumar Maurya (Environmental Science and Pollution Research, 2026)

Ficus benghalensis β-amylase: A potent biofilm-degrading enzyme with broad-Spectrum activity against nosocomial and foodborne pathogens - Anikesh Kumar; Deepshikha; Shailly Saini; Venkatesh Chaturvedi; Arvind M. Kayastha (Food Chemistry, 2026)

“Brewing Biopotency”: HRAMS and FTIR deconvolution of Butea monosperma-derived Kombucha - Suman Bharti; Dinesh Chandra Rai; Akansha Gupta; Arvind Kumar (Food and Humanity, 2026)

Germination behaviour and traits variability among nineteen graminoids of subtropical region of China - Arvind Bhatt; Harsh Kumar Chauhan; Cristina Blandino; Marcelo F. Pompelli; Luis E. Oviedo Zumaque; Richard Onalbi Hoyos-Lopez (Plant Ecology, 2026)

Dioscin-rich extract of Dioscorea floribunda ameliorates metabolic syndrome by improving inflammation-mediated gut, adipose and hepatic dysfunctions: a pre-clinical study - Sumati Sen; Aashcharya Uddeshya Mishra; Mridula Sahu; Mausam Singh; Nandini Pathak; Anil Kumar Gupta; Karuna Shanker; Arvind Singh Negi; Daya Nandan Mani; Dnyaneshwar Umrao Bawankule (Inflammopharmacology, 2026)

Microcystis aeruginosa detected in freshwater lakes in Meghalaya, India show strong hepatotoxicity - Waniabha J. Lyngdoh; Langpoklakpam James Singh; Ankita Dey; Divya Newar; Jopthiaw Nongdhar; Surya Bhan; Arvind Kumar Singh (Archives of Microbiology, 2026)

Synergistic effect of indigenous endophytes to boost nutritional content, quality traits and yield in tomato - K. R. Nayana; Sumit Deswal; Satish Kumar; Rahul Kumar Dhaka; Arvind Pratap Singh; Anuj Rana (Antonie van Leeuwenhoek, 2026)

Analysis of enzyme-based bioremediation approach in the degradation of high-energy materials (HEMs) for environmental restoration - Navneet Chhachhiya; Manvendu Mishra; S. Mary Celin; Vandana Mishra; Dipti Barui Bose; Arvind Kumar (Environmental Monitoring and Assessment, 2026)

Bacillus spp. and Jeotgalicoccus huakuii induce rice growth and salt stress resilience through eco-physiological adaptations - Sankalp Misra; Pradeep Semwal; Vaishali Umrao; Shashank Kumar Mishra; Pramod Arvind Shirke; Puneet Singh Chauhan (Environmental Sustainability, 2026)

Aptness of Lichen Hypotrachyna Cirrhata Biomass in Biosorption of Cu(II) from Synthetic Wastewater - Kirti Singh; Rajesh Puri Goswami; Arvind Kumar; Pushpa Joshi; Manoj Dhouni (Water, Air, & Soil Pollution, 2026)

Tandem mass spectrometry based study on the dissipation behaviour, dietary risk assessment and decontamination of chlorfenapyr, fenvalerate, and tolfenpyrad residues in broccoli - Sapna Katna; Preeti Bansal; Ajay Sharma; Tanuja Banshtu; Nisha Devi; Arvind Kumar; Shubhra Singh; Sakshi Sharma; Ankur Tomar (Environmental Geochemistry and Health, 2026)

Response of Strawberry (Fragaria × ananassa Duch.) to Plant Density and Column Size in a Vertical Soilless Cultivation System - Vikas Kumar Sharma; A. K. Godara; Deepak Kaushik; Krishan Kant Meena; Sushil Sharma; Adesh Kumar; Arvind Malik; Prince (Applied Fruit Science, 2026)

Doxorubicin-Induced Cardiotoxicity: Molecular Mechanisms to Novel Therapeutic Frontiers of Recent Preclinical Discoveries - Nandini Dubey; Satnam Singh; Pranav Panchbhai; Gauri Chaturvedi; Ahsas Goyal; Nirmal Singh; Jagriti Bhatia; Rajkumar Yadav; Sudhir Kumar Arava; Arvind Kumar; Mayank Yadav; Abhishek Yadav; et al. (Cell Biochemistry and Biophysics, 2026)

Contrasting boron dynamics in natural and managed land use systems of Himalayan realm - Pratibha Thakur; Nagender Pal Butail; Munish Sharma; Arvind K. Shukla; Sanjib K. Behera; Praveen Thakur; Pardeep Kumar (Soil and Tillage Research, 2026)

Effect of silage-based diets on growth performance, nutrient digestibility and carcass traits in Avishaan lambs - R.S. Bhatt; Srobana Sarkar; Arvind Soni; Lalit Kumar; M.C. Meena; Arun Kumar (Small Ruminant Research, 2026)

In silico retrieval of sulfiredoxin from Setaria italica, Panicum miliaceum, and Eleusine coracana: Sequence characterization, structural modeling, and protein–protein interaction analysis - Rahul Thakur; Arvind Gupta; Kanchan Rauthan; Deepti Dixit; Arzoo Choudhary; Ashutosh Kumar Pandey; Atul Krishna Dev; Saurabh Yadav (Plant Gene, 2026)

Palaeoenvironmental reconstruction from Hulas Khera: Insights into mid-late Holocene hydroclimatic variability in the Central Ganga Plain - Arvind Tiwari; Binita Phartiyal; M.C. Manoj; Masud Kawsar; K. Prasanna; Rajveer Sharma; Pankaj Kumar; Anupam Sharma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Multi-Objective Variance-Bias Tradeoff Optimization of ANN by Hybridizing with Multi-Objective GA for Water Discharge Estimation - Arvind Yadav; Ashwini Kumar Pradhan; Manish Kumar; Priyaranjan Sharma; Sunil Kr. Maakar; Shivangi Singh; Umamaheswararao Batta; Devendra Joshi (Water Resources Management, 2026)

Effect of Reclamation Approaches on the Soil Properties and Performance of the Rice-Wheat Cropping System Under Alkali Irrigation - Anu Sehrawat; Nirmalendu Basak; Arvind Kumar Rai; Priyanka Chandra; Parul Sundha; Sandeep Bedwal; Devvrat Dhiman; Mukesh Yadav; Rajender Kumar Yadav (Journal of Soil Science and Plant Nutrition, 2026)

Waste to Wealth: Acidulated Organic Manures for Enhanced Productivity and Nutrient–Supplying Capacity of Alkaline Soils - Sandeep Bedwal; Nirmalendu Basak; Arvind Kumar Rai; Parul Sundha; Priyanka Chandra; Dev Raj; Anita Mann; Subedar Patel; Harspreet Kaur; Sanjay Kumar; Raksh Vir Jasra; Rajender Kumar Yadav (Journal of Soil Science and Plant Nutrition, 2026)

In-Silico and Functional Characterization of EcdLp, an ABC Transporter of Aspergillus nidulans NRRL11440 - Shaurya Prakash; Arvind Kumar; Hemlata Kumari; Minakshi Sinha; Vinay Kumar; Antresh Kumar (Current Microbiology, 2026)

Classification of Wheat (Triticum aestivum) Cultivars for Iron Efficiency Under Western India Conditions - Dileep Kumar; Khushvadan C. Patel; Arvind Kumar Shukla; Sanjib Kumar Behera; Salwinder Singh Dhaliwal; Pradeep Kumar; Ravi A. Patel; Rahul Mishra; Ajay S. Bhanvadia (Agricultural Research, 2026)

Archean TTGs and high-K granitoids from the Madawara domain, Southern Bundelkhand Craton: Insights into petrogenesis, crustal growth, and mantle metasomatism - Pradip Kumar Singh; Ajay Kumar; Balaram Sahoo; Kumar Batuk Joshi; Sanjiv Kumar; Debajyoti Paul; Elson P. Oliveira; Dakshita; Vinod Kumar Singh; Arvind Kumar Gond; Archana Nikita Kispotta; Ishwar Chandra Rahi; et al. (Lithos, 2026)

MACM/FTIR spectroscopy: A new setup for flash pyrolysis of solid fuels and energetic materials - Shani Saha; Prathamesh Phadke; Rohit Sehrawat; Arvind Kumar; Arindrajit Chowdhury; Neeraj Kumbhakarna (Fuel, 2026)

Deciphering low nitrogen tolerance of wheat in mega-environments using integrated multivariate approaches - Gopalareddy Krishnappa; Hanif Khan; Amaresh; Vinayaka; T. Lakshmi Pathy; Arun Gupta; Anju Mahendru-Singh; Arvind Kumar Ahlawat; Jasavantlal Manilal Patel; Suma S. Biradar; Harohalli Masthigowda Mamrutha; Rinki Khobra; et al. (European Journal of Agronomy, 2026)

Erratum to “Numerical study of energy piles in unsaturated soils”. [Comput. Geotech. 189 (2026) 107619] - Arvind Kumar; Asal Bidarmaghz; Arman Khoshghalb (Computers and Geotechnics, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Enhancing hydrochar properties via co-hydrothermal carbonization of cooked food waste and human faeces using human urine as reaction medium in the Indian context: Synergistic effects and combustion performance - Zavin R. Gajera; Alka A. Mungray; Arvind Kumar Mungray (Bioresource Technology Reports, 2026)

Assessing the effect of engineered nanoparticles on microalgae Tetradesmus obliquus, for enhanced biomass production and CO2 sequestration - Faiz Ahmad Ansari; Arvind Kumar; Humeira Hassan; Abdul Gaffar Sheik; Ismail Rawat; Sheena Kumari; Faizal Bux (Bioresource Technology Reports, 2026)

Zinc Peroxide-based Carbon Composite for the Removal of Highly Toxic Insecticide Acetamiprid from Water - Shrawan Kumar; Harshit Gupta; Arvind Gautam; Nahar Singh (Water, Air, & Soil Pollution, 2026)

Analyzing soil loss dynamics in the Indian Himalayan Region using geospatial approach - Arvind Dhaloiya; Swadhina Koley; Manjar Alam; Soora Naresh Kumar (Spatial Information Research, 2026)

Therapeutic potential of phytochemicals against breast cancer: current status and future perspectives - Sangeeta Kumari; Victor Wilson Mattathi; Kalpana Thakur; Pushpak Dahiya; Ravi Kant Bhatia; Bharti Minhas; Arvind Kumar Bhatt; Neelam Kaushik (Phytochemistry Reviews, 2026)

Integrated computational-experimental pipeline for CHK1 inhibitor discovery: structure-based identification of novel chemotypes with anticancer activity - Dhanushya Gopal; Manasa Pacharla; Nehal Arvind Kumar; Prem Kumar; Angelin Preetha Sathiyanathan; Jaikanth Chandrasekaran; Mohit Agrawal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Whole Genome Sequencing and Subtractive Genomics of Lipaphis erysimi: A Vital Pest of Brassica juncea - Deepanshu Jayaswal; Ratna Prabha; Kuldeep Kumar; Deepesh Kumar; Kuldip Jayaswall; Archana Anokhe; Arvind Nath Singh; Sanjay Kumar; Rekha Kansal (Journal of Plant Growth Regulation, 2026)

Toxicity and Lethal Effect of Amaranthus powellii Extract Against the Polyphagous Pest Spilosoma obliqua (Lepidoptera: Arctiidae) Under Laboratory Conditions - Nilay Singh; Arvind Kumar; Promila Sharma; Manoj Kumar Pal; Neetu Sharma; Bhawana Bisht (Journal of Crop Health, 2026)

Assessing Cancer Risk from Wheat and Rice Based Diets in Arsenic Endemic Regions of the Middle Ganga Plain, India: Identification of Hotspots and Risk Reduction Strategies - Pragya Sharma; Sanjay Dwivedi; Sarvesh Kumar; Seema Mishra; Vishnu Kumar; Ruchi Agnihotri; Ravi Kumar Tiwari; Abhishek Niranjan; Pramod Arvind Shirke (Exposure and Health, 2026)

Nutraceutical powerhouses: leveraging α-amylase inhibitors for metabolic disease prevention - Avinash Kumar; Arvind M. Kayastha (Journal of Proteins and Proteomics, 2026)

Remediation of hazardous explosive-contaminated soil at field scale: a data-oriented review of technologies, challenges and recommendations - Garima Upreti; S. Mary Celin; Krishank Yadav; Anil K. Haritash; Dipti Barui Bose; Arvind Kumar (Environmental Monitoring and Assessment, 2026)

Integrated analysis of pesticide residue in brinjal and tomato using LC–MS/MS and DFT: dissipation behavior, consumer safety, and ecological risk - Arvind Kumar; Sujan Majumder; Manoj Dhouni; Rohit Kumar; Sudarshan Maurya; Arvind Nath Singh; Rajesh Kumar (Environmental Monitoring and Assessment, 2026)

Fabrication of Second-Generation Acalabrutinib Nanocrystals by Employing the Nano-Edge Method for Improving the Physico-Chemical Properties and Forecasting their In-Silico Pharmacokinetic Behaviour - Bharath M; Ujala Gupta; Anish Dhuri; Tanmoy Kanp; Khushi Rode; Sharon Munagalasetty; Vasundhra Bhandari; Soumyadip Mukherjee; Arvind Gulbake; Pankaj Kumar Singh (AAPS PharmSciTech, 2026)

Do the adoption of crop residue management technologies have favourable economic and environmental outcomes? Some insights from Indo-Gangetic Plains of India - Parvender Sheoran; Kiran Kumara TM; Ashish S. Murai; Suresh Kumar; Arvind Kumar; Rajbir Singh; Vinita Kanwal; Sandeep Kumar; Har Narayan Meena; Jai Parkash Mishra; Santanu K. Dubey; KJ Raghavendra; et al. (European Journal of Agronomy, 2026)

Numerical study of energy piles in unsaturated soils - Arvind Kumar; Asal Bidarmaghz; Arman Khoshghalb (Computers and Geotechnics, 2026)

Utilizing community-led citizen science in delineating population structure of an anadromous hilsa shad (Tenualosa ilisha) from Indian coastal shelf - Kritish De; Arvind Kumar Dwivedi (Continental Shelf Research, 2026)

Biodegradation of 2,4,6-trinitrotoluene by Biofilm Forming and Plant Growth Promoting Burkholderia gladioli: An Approach Towards Degradation Pathway Prediction - Aditya Roy; Urvi Santosh Mhadeshwar; Parry Dey; S. Mary Celin; Dipti B. Bose; Arvind Kumar; W. Jabez Osborne (Water, Air, & Soil Pollution, 2026)

Ranking and comparison of temperature-, mass transfer- and radiation based daily reference evapotranspiration models by using compromise programming index (CPI) and global performance indicator (GPI) - Abhishek Shukla; Arvind Singh Tomar; Kusum Pandey; Dinesh Kumar Vishwakarma; Siham Acharki; Ali Raza; Makrand Dhyani; Ozgur Kisi; Ahmed Z. Dewidar; Ahmed Al-Othman; Mohamed A. Mattar (Theoretical and Applied Climatology, 2026)

Genomic Characterization of F-box Genes in Pigeonpea (Cajanus cajan (L.) Millspaugh): Insights into Evolution, Synteny, and Spatio-Temporal Expression During Ovule/Seed Development - Kumari Arpita; Sandhya Sharma; Arvind Kumar Yadav; Machindra Nirgude; Mohammad Israil Ansari; Kishor Gaikwad (Journal of Plant Growth Regulation, 2026)

Soil–Water Retention and Microstructural Evolution of Lime-Treated Highly Compressible Soil amended with Nano Clay - Ajeet Kumar; Neeraj Kumar; Arvind Kumar Jha (Geotechnical and Geological Engineering, 2026)

Correction: Sustainable management of near‑field blast‑induced ground vibration for elevating limestone extraction potential in Indian mines‑ A case study - Aditya Rana; Arvind Kumar Gond; Saikat Banerjee; Deepak Kumar Tiwari; C. Sawmliana (Environmental Geochemistry and Health, 2026)

Bael (Aegle marmelos Correa): a resilient fruit tree for sustainable horticulture in semi-arid ecosystem - Arvind Kumar Singh; Lalu Prasad Yadav; Hare Krishna; Chet Ram; K. Gangadhara; Jagadish Rane; Anil Pawar; Anand Sahil; P. Ravat (Vegetos, 2025)

Assessing the soil organic carbon stability and greenhouse gases mitigation in rice-wheat system: Seventeen-years assessment of tillage and residue management - Ram K. Fagodiya; Kamlesh Verma; Gargi Sharma; Arvind Kumar Rai; Kailash Prajapat; Ranbir Singh; Parvender Sheoran; Nirmalendu Basak; Priyanka Chandra; D.P. Sharma; R.K. Yadav; A.K. Biswas (Soil and Tillage Research, 2025)

Immobilized pigeon pea urease on chitosan-PEG biocomposite for concurrent urea sensing in milk and blood samples - Prince Kumar; Aditya Ghosal; Arvind M. Kayastha (Food Chemistry, 2025)

Spatio-temporal patterns of habitat suitability for two exotic fishes under climate change in a tropical river basin - Arvind Kumar Dwivedi; Kritish De (Ecohydrology & Hydrobiology, 2025)

“Geometric Morphometric” Approach To Detect Body Shape Variations among Three Indian Shads - Kritish De; Arvind Kumar Dwivedi (Thalassas: An International Journal of Marine Sciences, 2025)

Critical Magnesium Levels in Soil and Potato (Solanum tuberosum) Plants Grown on Lateritic Red Soils - Chitdeshwari T; Viveka B; Arvind Kumar Shukla; Sanjib Kumar Behera (Potato Research, 2025)

Sustainable management of near-field blast-induced ground vibration for elevating limestone extraction potential in Indian mines- A case study - Aditya Rana; Arvind Kumar Gond; Saikat Banerjee; Deepak Kumar Tiwari; C. Sawmliana (Environmental Geochemistry and Health, 2025)

Microbial fuel cell mediated azo dye degradation: a comprehensive review on anode, cathode, membrane interfaces and scale-up potential - Parini Vrajesh Surti; Suresh Kumar Kailasa; Dipak A. Jadhav; Arvind Kumar Mungray (Reviews in Environmental Science and Bio/Technology, 2025)

Residues of lambda-cyhalothrin and novaluron in Brassica oleracea L. var. italica Plenck: method validation, residual behaviour and dietary risk assessment - Sakshi Sharma; Sapna Katna; Ajay Sharma; Pankaj Sharma Istatu; Nisha Devi; Arvind Kumar; Shubhra Singh (Journal of Consumer Protection and Food Safety, 2025)

Molecular insights into GnRH3-associated peptide structure and reproductive responses in Channa striata stimulated with sGnRH analogue - Prachi Asgolkar; Kiran D. Rasal; Rajesh Kumar; Uday Udit; Arvind Sonwane; Manoj Brahmane; Sunil Kumar; Mayank Rashmi; Girish Kumar Jha; Jitendra Kumar Sundaray; Megha Bedekar; Mukunda Goswami (Aquaculture International, 2025)

New distribution record of nicobar rustic, Cupha erymanthis nicobarica felder (Lepidoptera: Nymphalidae) from Northern India and its biology study on newly recorded host plant, Populus deltoides Bartr. ex marsh - Arvind Kumar; Tripti Tonk (International Journal of Tropical Insect Science, 2025)

Steroidal glycoside-rich extract of fenugreek seeds mitigates obesity-induced insulin resistance via attenuation of low-grade inflammation - Sumati Sen; Ashutosh K. Tiwari; Monika Binwal; Monazza Israr; Anant Kumar; Nandini Pathak; Kaveri R. Washimkar; CH Ratnasekhar; Madhav Nilakanth Mugale; Arvind S. Negi; Dnyaneshwar U. Bawankule (Food Research International, 2025)

Sex-Dependent Regional Vulnerability and Recovery Mechanisms in a Mouse Model of Transient Global Cerebral Ischemia - Debiprasad Sinha; Roli Kushwaha; Shashikant Patel; Sainath Sunil Dhaygude; Mydhili Radhakrishnan; Papia Basuthakur; Arvind Kumar; Sumana Chakravarty (NeuroMolecular Medicine, 2025)

Decline in C:N:P ratios of particulate organic matter during the fall intermonsoon in the northern Indian Ocean - Deepika Sahoo; Sipai Nazirahmed; Sanjeev Kumar; Arvind Singh (Progress in Oceanography, 2025)

Mechanistic behavior of fenugreek α-amylase on starch hydrolysis upon interaction with Hesperetin and Luteolin probed by multispectroscopic and in silico approaches - Ranjana Das; Avinash Kumar; Vinay Singh; Arvind M. Kayastha; Chandan Singh (Food Chemistry, 2025)

Enhanced bioethanol production from sequential alkali-laccase-hydroxybenzotriazole pretreatment and additive-mediated saccharification in kenaf (Hibiscus cannabinus L.) - Laxmi Sharma; Pratik Satya; Binita Dev; Tinku Goswami; Nurnabi Meherul Alam; Suman Roy; Arvind Kumar Singh; Surendra Kumar Pandey; Bijan Majumdar; A.K. Lavanya; Gouranga Kar (Biomass and Bioenergy, 2025)

Exploring residue profiles and risk assessment of azoxystrobin and chlorothalonil in peas (Pisum sativum L.) - Sapna Katna; Tanuja Banshtu; Shubhra Singh; Nisha Devi; Arvind Kumar; Sakshi Sharma (Environmental Geochemistry and Health, 2025)

Maternal effects upon early stages of Panicum turgidum and Pennisetum divisum (Arabian Desert Grasses): implications for improving desert restoration efficiency - Arvind Bhatt; Paulo Roberto de Moura Souza Filho; Harsh Kumar Chauhan (Biologia, 2025)

QbD-driven extraction and purification of piceatannol from passion fruit seeds and its cubosomes development, characterization, and neuronal cellular analysis - Navratan Soni; Sandeep Jat; Ankaj Kumar; Arvind Gulbake; Manini Bhatt; Bodhisatwa Das; Ramkishore Matsa; Pratik Vilas Gore; Dnyaneshwar Maykar; Pramod Kumar (Food Bioscience, 2025)

Synergistic π-π interactions boosted removal of tetracycline from water by dual-aromatic hydrophobic deep eutectic solvents - Sajith Babu M K; Gohil Mrunaliniba Yuvrajsinh; Madhumitha Manickasundaram; Arvind Kumar; Srinivasarao Kancharla (Chemical Engineering Journal, 2025)

An exploration of lipid remodeling by microalga Chlamydomonas reinhardtii in autotrophic and mixotrophic cultivation for bioenergy prospects - Avinash Singh; Savita Singh; Nitesh Prasad; Sakshi Singh; Abhishek Mohanta; Arvind M. Kayastha; Ravi Kumar Asthana (Biomass and Bioenergy, 2025)

Dissipation pattern, risk assessment and decontamination of residues of emamectin benzoate, fipronil and acetamiprid on bell pepper - Arzoo Bakshi; Ajay Sharma; Sapna Katna; Tanuja Banshtu; Nisha Devi; Arvind Kumar; Shubhra Singh; Sakshi Sharma; Pankaj Istatu Sharma; Ankur Tomar; Muskan Baltoo (Environmental Geochemistry and Health, 2025)

Enhancing solar radiation forecasting accuracy with a hybrid SA-Bi-LSTM-Bi-GRU model - Girijapati Sharma; Subhash Chandra; Arvind Kumar Yadav; Rahul Gupta (Earth Science Informatics, 2025)

Evaluating urban bioclimatic comfort in a metropolitan city Kolkata with urban dynamics and heat Islands - Bikash Ranjan Parida; Khushi Prasad; Sagar Kumar Swain; Chandra Shekhar Dwivedi; Arvind Chandra Pandey; Kishore Chandra Swain (Advances in Space Research, 2025)

Studies on volume based mass modelling and physicochemical properties of wild bitter apple (Citrullus colocynthis L.) fruits grown in the semi-arid region of Punjab - Shilpa S Selvan; Amit Nath; Mahesh Kumar Samota; Arvind Kumar Ahlawat (Vegetos, 2025)

Addressing material uncertainty in reliability analysis of floating offshore mooring through probabilistic meta-model developed with Stochastic Kriging technique - Rohit Kumar; Kala J. Prasad; Arvind Keprate; Subhamoy Sen (Ocean Engineering, 2025)

Efficient microplastic removal from wastewater using Fe3O4 functionalized g-C3N4 and BNNS: A comprehensive study - Riona Indhur; Arvind Kumar; Faizal Bux; Sheena Kumari (Journal of Environmental Chemical Engineering, 2025)

Photocatalysis-self-Fenton based oxidation system towards the reclamation of recalcitrant pollutants: Current advances and future prospects - Akash Balakrishnan; Emmanuel Sebastian Kunnel; Nanditha Dayanandan; Hritankhi Tripathy; Mahendra Chinthala; Arvind Kumar; Dai-Viet N. Vo (Journal of Environmental Chemical Engineering, 2025)

Peroxymonosulfate-activated photocatalytic reclamation of sulfamethoxazole using In₂S₃/CuSe infused carboxymethyl cellulose photocatalytic heterojunction hydrogels: Insights into operations and mechanisms - Hritankhi Tripathy; Akash Balakrishnan; Mahendra Chinthala; Arvind Kumar (Chemical Engineering Journal, 2025)

Hybrid membrane technology with renewably derived biological and photocatalytic systems for wastewater treatment - Pragati Awasthi; Gunjan Kumar Agrahari; Akanksha Patel; Arvind Singh (Biodegradation, 2025)

Diverse land use systems differentially affect soil quality index in reclaimed sodic soils of Western Indo-Gangetic plains of India - Renu Kumari; Ram Kishor Fagodiya; Gargi Sharma; Kamlesh Verma; Raj Kumar; Kailash Prajapat; Indu Shekhar Thakur; Arvind Kumar Rai; Rajender Kumar Yadav (Agroforestry Systems, 2025)

Morphometric analysis of Parthenium beetle, Zygogramma bicolorata (Pallister) under thermal-stress conditions - Arvind Kumar Patel; Priyanka Yadav; Bhupendra Kumar (International Journal of Tropical Insect Science, 2025)

Drivers of local contribution to beta diversity of fish communities in a tropical river basin of Indian Deccan Plateau - Arvind Kumar Dwivedi; Kritish De (Ecohydrology & Hydrobiology, 2025)

Identification and comprehensive genomic characterization of cellulolytic Bacillus species reveal unique CAZyme profiles for leaf litter degradation and compost production - Arvind Kumar Singh; Subhojit Datta; Girindrani Dutta; Tinku Goswami; Pranit Mukherjee; Bijan Majumdar; Gouranga Kar (World Journal of Microbiology and Biotechnology, 2025)

Insecticidal, antifeedant, growth inhibitory effects, and molecular docking of Ageratina adenophora extract against Spilosoma obliqua - Nilay Singh; Arvind Kumar; Manoj K. Pal; Ashutosh Pal; Promila Sharma (Phytoparasitica, 2025)

Development of Stomata and Trichomes is Correlated with Improved Water Use Efficiency in Cluster Bean [Cyamopsis tetragonoloba (L.) Taub.] Under Drought - Shiv Narayan; Anil Kumar; Pramod Arvind Shirke (Journal of Plant Growth Regulation, 2025)

Acidulated composts govern the soil solution nutrient composition through changes in key functional bacterial community of alkaline soils - Sandeep Bedwal; Arvind Kumar Rai; Nirmalendu Basak; Priyanka Chandra; Parul Sundha; Amresh Chaudhary; Harshpreet Kaur; Subedar Patel; Sanjay Kumar; Rajender Kumar Yadav (Applied Soil Ecology, 2025)

Elucidating neural molecular mechanisms underlying metabolic disorders-induced neuropsychiatric disorders in mice on prolonged high fructose diet - Sachin Singh; Nitesh Kumar Singh; Kottapalli Srividya; Unis Ahmad Bhat; Divya Tej Sowpati; Sumana Chakravarty; Arvind Kumar (Metabolic Brain Disease, 2025)

Optimization and evaluation of Eisenia fetida based vermicompost derived from fish processing waste, rice straw, and biogas slurry for sustainable agriculture - Swati Kumari; Rohit Kumar Singh; Arvind Singh; Abhay Kumar Choubey; Praveen Kumar Srivastava (Process Safety and Environmental Protection, 2025)

Functional complexity of Parthenium beetle, Zygogramma bicolorata (Pallister) under thermal-stress conditions: Insights from Gene Ontology - Arvind Kumar Patel; Bhupendra Kumar (Journal of Asia-Pacific Entomology, 2025)

Dynamic Response of Grouted Jointed Rock Mass to Cyclic Loading Under Extreme Temperature Conditions - Gaurav Kumar Mathur; Arvind Kumar Jha; Gaurav Tiwari; T. N. Singh (Rock Mechanics and Rock Engineering, 2025)

Deciphering salt stress response of pomegranate genotypes (Punicagranatum L.): a comprehensive evaluation - Chandrakant Awachare; Janhavi Pravin Patel; Sebin Sara Solomon; Pinky Raigond; K. Dhinesh Babu; Shilpa Parashuram; Susheel Kumar Sarkar; Mahesh Kumar; C. T. Manjunath Prasad; Rajiv Arvind Marathe; Nripendra Vikram Singh (Plant Physiology Reports, 2025)

Mitigating Salinity Stress in Crops using Talaromyces sp.: Impacts on Phosphorus Solubilization, Growth and P Nutrition - Priyanka Chandra; Arvind Kumar Rai; Nirmalendu Basak; Parul Sundha; Sandeep Bedwal; Kailash Prajapat; Rajender Kumar Yadav (Journal of Soil Science and Plant Nutrition, 2025)

Geostatistics-Based Understanding of Temporal Changes In Spatial Distribution of Soil Fertility Parameters In An Intensively Cultivated Area of North India - Sanjib Kumar Behera; Arvind Kumar Shukla; Rohtas Kumar; Rahul Mishra; Vimal Shukla; Harendra Yadav; Siba Prasad Datta (Journal of Soil Science and Plant Nutrition, 2025)

Statistical and experimental prediction of bending strength with partial replacement of waste plastic using response surface method (Minitab) and artificial neural network (Matlab) in concrete - C. Arvind Kumar; Y. Suvidha; Sumesh Jain (Innovative Infrastructure Solutions, 2025)

Biotic Stress Alleviation in Plant Using Rhizobacteria: An Overview of Mechanism of Action, Antimicrobial Compounds Production, (Nano) Formulations and Employment Methods - Anuj Rana; Annu Rani; KR. Nayana; Sumit Deswal; Arvind Pratap Singh; Sravendra Rana; Madhvi Chahar; Namita Singh; Rahul Kumar Dhaka (Indian Journal of Microbiology, 2025)

Development of breeding lines with multiple stress tolerance to cold, drought, and high-temperature stress in rice (Oryza sativa L.) - Rahul Priyadarshi; Shailesh Yadav; Mamatha Pettem; Challa Venkateshwarlu; K. J. Pranesh; Vikas K. Singh; Arvind Kumar (Euphytica, 2025)

Polyphenol oxidase (PPO) in wheat (Triticum aestivum): a systematic review on bioactivity, inheritance, functionality and their effects on end products - Rajappa Harisha; Adithya P. Balakrishnan; Karthik Kumar Manjunath; Beera Bhavya; Shaily Singhal; Harshitha Bheemapura Shivakumar; Arvind Kumar Ahlawat; Sanjay K. Singh; Anju Mahendru Singh (Cereal Research Communications, 2025)

Residue dynamics and food safety evaluation of novel insecticides on tomato fruit - Chada Anu Reddy; Mahesh Pathak; Yengkhom Bijen Kumar; Kennedy Ningthoujam; Jyotim Gogoi; Abhinay; Arvind Kumar; Bimal Kumar Sahoo; Sharad Sharma; Pradeep Kumar Chandra; Sujan Majumder (Environmental Monitoring and Assessment, 2025)

Mechanisms behind the post harvest sprouting of onions (allium cepa) and future implications of prevention strategies - Mahesh Kumar Samota; Shilpa S. Selvan; Poonam Choudhary; Amit Nath; Arvind Ahlawat; Varinda (Journal of Stored Products Research, 2025)

Development of a NIRS-based prediction model for measurement of whole wheat flour arabinoxylan content to aid rapid germplasm screening - Adithya P. Balakrishnan; Antil Jain; Sumit Kr Singh; Arvind Kumar Ahlawat; Jai Prakash Jaiswal; Anju Mahendru-Singh; Rakesh Bhardwaj (Journal of Cereal Science, 2025)

Diesel purification through imidazole-based deep eutectic solvents: Desulfurization, dearomatization, and denitrogenation - Sajith Babu MK; Sanjay Mehra; Arvind Kumar; Srinivasarao Kancharla (Fuel, 2025)

Harnessing genotype × environment interaction and advanced selection indices for nutritional enhancement in taro (Colocasia esculenta (L.) Schott) - Vijay Bahadur Singh Chauhan; Hanume Gowda Krishnappa; Pinki Mohapatra; Samarendra Narayan Mallick; Maniyam Nedunchezhiyan; Byju Gangadharan; Manas Ranjan Sahoo; Kalidas Pati; Rameshkumar Arutselvan; Mohammad Shahid; Arvind Kumar Verma (Food Chemistry, 2025)

HR-MS-based bioactive profiling of green Banana flour and millets-based Murukku snack - Tomaly Saha; Manish Kumar Singh; Dinesh Chandra Rai; Arvind Kumar (Food and Humanity, 2025)

Combined Genome-Wide Association Study and Expression Analysis Unravels Candidate Genes Associated with Seed Weight in Moth Bean [Vigna aconitifolia (Jacq.) Marechal] - Arvind Kumar Yadav; Chandan Kumar Singh; Dhammaprakash P. Wankhede; Rajwant K. Kalia; Seema Pradhan; Shraddha Ujjainwal; Tanmaya Kumar Sahu; N. S. Nathawat; R. K. Kakani; Reena Rani; Rajesh Kumar; Rakesh Pathak; et al. (Journal of Plant Growth Regulation, 2025)

Influence of pruning intensity on growth, yield and bio-chemical parameters of guava (Psidium guajava L.) Cv. Shweta under North Indian conditions - Vibhu Pandey; Arvind Kumar; Khushboo Sharma; Deepesh Keshari; Amit Kumar; Devendra Pal (Vegetos, 2025)

Mapping iron oxides with Landsat-8/OLI imagery from iron ore deposit in Singhbhum craton, eastern India: Its implication to mineral exploration - Arvind Chandra Pandey; Sagar Kumar Swain; Chandra Shekhar Dwivedi (Ore and Energy Resource Geology, 2025)

Comprehensive profiling and risk assessment of antibiotic resistomes in surface water and plastisphere by integrated shotgun metagenomics - Muneer Ahmad Malla; Malambule Nomalihle; Jonathan Featherston; Arvind Kumar; Isaac D. Amoah; Arshad Ismail; Faizal Bux; Sheena Kumari (Journal of Hazardous Materials, 2025)

Transcriptome Analysis Reveals Differential Gene Regulation in Ovarian Tissues of Anabas testudineus (Bloch, 1792) in Response to Insecticide, Monocrotophos - Siyag A. Dhere; Pokanti Vinay Kumar; Kiran D. Rasal; Sujata Mohapatra; Prachi Asgolkar; Manohar Vasam; Sheetal Vanjre; Priyanka S. S.; Manoj P. Brahmane; Arvind Sonwane; Rajesh Kumar; Naresh S. Nagpure; et al. (Marine Biotechnology, 2025)

Assessing fracture mechanics in thermally treated, uniaxial loaded grouted non-persistent medium-hard rock: a digital image correlation and FracPaQ analysis - Gaurav Kumar Mathur; Arvind Kumar Jha; Gaurav Tiwari (Bulletin of Engineering Geology and the Environment, 2025)

Dual Drug Loaded Topical Cubosomal Gel Against Candida Albicans: An In Vitro and In Vivo Proof of Concept - A. Gowri Nath; Klaudi K. Vaiphei; Ankaj Kumar; Sargun Basrani; Ashwini Jadhav; Rudra Chakravarti; Dipanjan Ghosh; Kuldeep K. Bansal; Arvind Gulbake (AAPS PharmSciTech, 2025)

The role of industry 4.0 enabling technologies for predicting, and managing of algal blooms: Bridging gaps and unlocking potential - Abdul Gaffar Sheik; Mantena Sireesha; Arvind Kumar; Purushottama Rao Dasari; Reeza Patnaik; Sourav Kumar Bagchi; Faiz Ahmad Ansari; Faizal Bux (Marine Pollution Bulletin, 2025)

Promoting green healthcare initiatives: A systematic literature review, conceptual framework and future research agenda - Manas Sahoo; Arvind Kumar; Vikas Thakur (Journal of Cleaner Production, 2025)

Effective Biomixture for Preventing Pesticide Point Source of Contamination - Kumari Divya Jyoti; Pritam Ganguly; Arnab Goon; Munna Kumar; Rajat Kumar Roy; Arvind Kumar; Mainak Ghosh; Rajiv Rakshit (Journal of Soil Science and Plant Nutrition, 2025)

Evaluation of ecological risk due to suspended particulate matter-bound heavy metals deposited on selected plants in an urban area - Durga Prasad Tripathi; Arvind Kumar Nema (Urban Climate, 2025)

Substantial invasion of Antarctic Intermediate Water into the Arabian Sea during Younger Dryas and Heinrich Stadials - Arvind Shukla; Tapas Kumar Mishra; Sunil Kumar Singh; Arun Deo Singh (Quaternary Science Reviews, 2025)

Innovative synthesis approaches and health implications of organic-inorganic Nanohybrids for food industry applications - Ranjana Das; Avinash Kumar; Chandan Singh; Arvind M. Kayastha (Food Chemistry, 2025)

Photocatalytic self-Fenton degradation of tetracycline over Z-scheme functionalized g-C3N4/CeO2/Bi2S3 hydrogel beads: Dynamics, mechanism, degradation pathways and toxicity analysis - K. Vijaya Suryaa; Akash Balakrishnan; Mahendra Chinthala; Khwairakpam Bidya Devi; Hritankhi Tripathy; Arvind Kumar; Tejraj M. Aminabhavi; Sami Rtimi (Chemical Engineering Journal, 2025)

Anisotropic Rock Mass Characterization: A Directional-Continuous Rating System - Gowtham Ganesan; Arvind Kumar Mishra (Geotechnical and Geological Engineering, 2025)

Real-time fatigue assessment of Floating Offshore Wind Turbine Mooring employing sequence-to-sequence-based deep learning on indirect fatigue response - Rohit Kumar; Subhamoy Sen; Arvind Keprate (Ocean Engineering, 2025)

Evaluation of the stability and fate of biogenic selenium-laden waste generated as treatment residual in selenium removing sulfidogenic bioreactors - Arvind Kumar Shakya; Saleeq V P; Pranab Kumar Ghosh (Journal of Cleaner Production, 2025)

Coupled heat and moisture migration in unsaturated soils subjected to thermal gradients - Arvind Kumar; Asal Bidarmaghz; Arman Khoshghalb; Kenichi Soga (Computers and Geotechnics, 2025)

A Z-scheme defect-rich and dimensionally confined double functionalized g-C3N4 homojunction pectin hydrogels for the photocatalysis-self-Fenton-peroxymonosulfate system: Unraveling synergistic catalysis and reaction mechanism - Akash Balakrishnan; Mahendra Chinthala; Arvind Kumar; Damia Barceló; Sami Rtimi (Chemical Engineering Journal, 2025)

Retraction notice to “Fabrication of thermostable and reusable nanobiocatalyst for dye decolourization by immobilization of lignin peroxidase on graphene oxide functionalized MnFe2O4 superparamagnetic nanoparticles” [Bioresour. Technol. 317 (2020) 124020] - Kiran; Ranju Kumari Rathour; Ravi Kant Bhatia; Dilbag Singh Rana; Arvind Kumar Bhatt; Nagesh Thakur (Bioresource Technology, 2025)

Recent advances in mechanistic insights into microplastics mitigation strategies via emerging advanced oxidation processes: Legislation, challenges, and future direction - Arvind Kumar; Riona Indhur; Faizal Bux; Sheena Kumari (Science of The Total Environment, 2024)

Selenium and concomitant anions removal in a fixed bed bioreactor to satisfy drinking water regulations and subsequent stability check of selenium-laden biosludge - Arvind Kumar Shakya; Himanshu Sonkeshariya; Gajjela Rajashekhar; Pranab Kumar Ghosh (Environmental Research, 2024)

Valorization of agri-wastes through microbial consortia and its conversion into bioethanol by co-fermentation method using Saccharomyces cerevisiae NCIM 3594 and Pichia stipitis NCIM 3497 strains - Pawale Amol Vishwas; Arvind Kumar; Khem Raj Meena (Bioresource Technology Reports, 2024)

Assessment of feeding hydroponic fodder on growth and reproduction performance in Black Bengal goat - Shailendra Kumar Rajak; Arvind Kumar Singh; Abhishek Kumar Singh; Asish Rai; Anshu Gangwar (Tropical Animal Health and Production, 2024)

Guardians of the Gut: Harnessing the Power of Probiotic Microbiota and Their Exopolysaccharides to Mitigate Heavy Metal Toxicity in Human for Better Health - Pushpak Dahiya; Sangeeta Kumari; Manya Behl; Aakash Kashyap; Deeksha Kumari; Kalpana Thakur; Mamta Devi; Neelam Kumari; Neelam Kaushik; Abhishek Walia; Arvind Kumar Bhatt; Ravi Kant Bhatia (Probiotics and Antimicrobial Proteins, 2024)

Association of nitrogen utilisation efficiency with sustenance of reproductive stage nitrogen assimilation, transcript abundance and sequence variation of nitrogen metabolism genes in rice (Oryza sativa L.) sub-species - B. Jagadhesan; Hari S. Meena; Shailendra K. Jha; K. G. Krishna; Santosh Kumar; Allimuthu Elangovan; Viswanathan Chinnusamy; Arvind Kumar; Lekshmy Sathee (Plant Physiology Reports, 2024)

Characterization of Alternaria blotch disease of apple in Himachal Pradesh, India: insights on morphology, pathogenicity, and molecular features - Praneet Chauhan; Arvind Kumar Gupta; Jagan Nath Sharma; Monica Sharma (Molecular Biology Reports, 2024)

Dissecting genetic variation for agro-morphological traits of elevated temperature under CO2-temperature gradient chamber and validation of markers linked to heat tolerance of rice (Oryza sativa L.)‏ cultivars of north-eastern Himalayan Region - Amit Kumar; Letngam Touthang; Shankar. P. Das; R. Krishnappa; Avinash Pandey; Arvind Prasad; Shiv Poojan Singh; Simardeep Kaur; C. Aochen; Veerendra Kumar Verma; N. Umakanta; A. Gangarani Devi; et al. (Euphytica, 2024)

QTL mapping reveals different set of candidate genes governing stable and location specific QTLs enhancing zinc and iron content in rice - Sonali Vijay Habde; Shravan Kumar Singh; Dhirendra Kumar Singh; Arun Kumar Singh; Rameswar Prasad Sah; Mounika Korada; Amrutlal R. Khaire; Prasanta Kumar Majhi; Uma Maheshwar Singh; Vikas Kumar Singh; Arvind Kumar (Euphytica, 2024)

Reinvigorating algal cultivation for biomass production with digital twin technology - a smart sustainable infrastructure - Abdul Gaffar Sheik; Arvind Kumar; Faiz Ahmad Ansari; Vinay Raj; Nicolás M Peleato; Ameer Khan Patan; Sheena Kumari; Faizal Bux (Algal Research, 2024)

Transcriptomic Profiling Reveals Sex-Specific Epigenetic Dynamics Involving kdm6b and H3K27 Methylation in Cerebral Ischemia-Induced Neurogenesis and Recovery - Mydhili Radhakrishnan; Aditya Undru; Shashikant Patel; Pooja Sharma; Arvind Kumar; Sumana Chakravarty (NeuroMolecular Medicine, 2024)

Machine learning-based monitoring and design of managed aquifer rechargers for sustainable groundwater management: scope and challenges - Abdul Gaffar Sheik; Arvind Kumar; Anandan Govindan Sharanya; Seshagiri Rao Amabati; Faizal Bux; Sheena Kumari (Environmental Science and Pollution Research, 2024)
Managed aquifer recharge (MAR) replenishes groundwater by artificially entering water into subsurface aquifers. This technology improves water storage, reduces over-extraction, and ensures water security in water-scarce or variable environments. MAR systems are complex, encompassing various components such as water storage, soil, meteorological factors, groundwater management (GWM), and receiving bodies. Over the past decade, the utilization of machine learning (ML) methodologies for MAR modeling and prediction has increased significantly. This review evaluates all supervised, semi-supervised, unsupervised, and ensemble ML models employed to predict MAR factors and parameters, rendering it the most comprehensive contemporary review on this subject. This study presents a concise and integrated overview of MAR’s most effective ML approaches, focusing on design, suitability for water quality (WQ) applications, and GWM. The paper examines performance measures, input specifications, and the variety of ML functions employed in GWM, and highlights prospects. It also offers suggestions for utilizing ML in MAR, addressing issues related to physical aspects, technical advancements, and case studies. Additionally, previous research on ML-based data-driven and soft sensing techniques for MAR is critically evaluated. The study concludes that integrating ML into MAR systems holds significant promise for optimizing WQ management and enhancing the efficiency of groundwater replenishment strategies.

NIR Light-triggered Green Emitting Perovskite-based Phosphor for Optical Thermometry and Future Molecular Logic Gate Applications - Ishant Kumar; Avinash Kumar; Sandeep Kumar; Govind B. Nair; H. C. Swart; Arvind K. Gathania (Journal of Fluorescence, 2024)

Exposure to traffic and greenspace, and associations with respiratory health in urban India - Sowmya Malamardi; Katrina Lambert; Sheetu Singh; Sundeep Salvi; Sushil K. Kabra; Meenu Singh; Shally Awasthi; Arvind Kumar Sharma; Sabir Mohammed; Thevaruparambil U. Sukumaran; Aloke G. Ghoshal; Nishtha Singh; et al. (Urban Climate, 2024)

Yeast based biorefinery for xylitol and ethanol production from sugarcane bagasse - Vishal Ahuja; Sampath Chinnam; Arvind Kumar Bhatt (Process Safety and Environmental Protection, 2024)

Degradation of tetracycline via peroxymonosulfate activation by highly reusable Titanium dioxide/impregnated Zirconium-chitosan beads - Akash Balakrishnan; Vijaya Suryaa K; Raksha Marskole; Mahendra Chinthala; Arvind Kumar (Journal of Environmental Management, 2024)

Fourteen-years impact of crop establishment, tillage and residue management on carbon input, soil carbon sequestration, crop productivity and profitability of rice-wheat system - Ram K. Fagodiya; Gargi Sharma; Kamlesh Verma; Ajay Singh; Ranbir Singh; Parvender Sheoran; Arvind Kumar Rai; Kailash Prajapat; Suresh Kumar; Priyanka Chandra; Sonia Rani; D.P. Sharma; et al. (European Journal of Agronomy, 2024)

Antifungal, antibacterial and antioxidant activity of Pinus roxburghii mediated green synthesized zinc and gadolinium doped manganese oxide nanoparticles - Meena Devi; Sheetal Sharma; Pankaj Kumar; Nikesh Thakur; Gulshan Kumar; Manu Vineet Sharma; Arti Jamwal Sharma; Kuldeep Kumar; Arvind Sharma; Kamal Jeet; Naveen Thakur (Colloids and Surfaces C: Environmental Aspects, 2024)

Development of applicator to deliver hydrogel precursor powder for esophageal stricture prevention after endoscopic submucosal dissection - Takeshi Fujiyabu; Pan Qi; Kenichi Yoshie; Ayano Fujisawa; Yosuke Tsuji; Arvind Kumar Singh Chandel; Athira Sreedevi Madhavikutty; Natsuko F. Inagaki; Seiichi Ohta; Mitsuhiro Fujishiro; Taichi Ito (Chemical Engineering Journal, 2024)

Cavitation-assisted synthesis and chracterization of a novel catalyst from waste coconut trunk biomass for biodiesel production - A.V.S.L. Sai Bharadwaj; Sampath Chinnam; Jason Joseph Phillips; V. Janani; K.S. Gajendra; V. Archana; Arvind Singh Chauhan; Navneet Kumar Gupta (Bioresource Technology, 2024)

Potential impact of climate change on water productivity and water footprints of rice and wheat in the Indo-Gangetic plains of India - Gouranga Kar; Arvind Kumar Singh; Debarati Datta (Environmental Monitoring and Assessment, 2024)

Nanopriming with phytofabricated selenium nanoparticles alleviates arsenite-induced oxidative stress in Spinacia oleracea L - Amit Kumar; Garima Jain; Prasanna Dutta; Puja Singh; Naushad Alam; Shiv Narayan; Pramod Arvind Shirke; Debasis Chakrabarty (Environmental Science and Pollution Research, 2024)

Effect of metakaolin and lime addition on geopolymerization of construction and demolition waste - Arvind Pathak; Sanjay Kumar; Vinay Kumar Jha (Environmental Science and Pollution Research, 2024)

Characterization of biotic and abiotic signatures of modern lake sediments of western India, and its palaeo-environmental implications - Anjali Trivedi; Sheikh Nawaz Ali; M.C. Manoj; Shailesh Agrawal; Anupam Sharma; Binita Phartiyal; Kamlesh Kumar; Arvind Tiwari; P. Morthekai; Biswajeet Thakur; Anjum Farooqui; Mohd Ikram; et al. (Quaternary International, 2024)

Discerning the role of a site cation in ACoO3 perovskites for boosting Co3+/Co2+ redox cycle for pollutant degradation: DFT calculation, mechanism and toxicity evolution - Arvind Kumar; Abdul Ahamad; Basheshwer Prasad; Faizal Bux; Sheena Kumari (Environmental Research, 2024)

Optimization of Deficit Irrigation Water Usage for Maximisation of Jute Fibre Yield Using the Soil-water-crop Model in a Sub-tropical Climate - Debarati Datta; Arvind Kumar Singh; Girindrani Dutta; Nurnabi Meherul Alam; Dhananjay Barman; Ranjan Kumar Naik; Sourav Ghosh; Gouranga Kar (Water Resources Management, 2024)

A novel mutation in non-constitutive lycopene beta cyclase (CstLcyB2a) from Crocus sativus modulates carotenoid/apocarotenoid content, biomass and stress tolerance in plants - Javid Ahmad Mir; Arvind Kumar Yadav; Deepika Singh; Nasheeman Ashraf (Planta, 2024)

Geospatial analysis of elephant habitat suitability and movement for mapping the elephant corridor in Dalma Wildlife Sanctuary (India) - Satendra Kumar Chaudhary; Arvind Chandra Pandey; Bikash Ranjan Parida (Environmental Monitoring and Assessment, 2024)

An in-depth analysis of factors and forecasting techniques for emerging solid waste streams - Amim Altaf Nabi; Arvind Kumar Nema (Journal of Environmental Management, 2024)

Enhancing milk quality assessment with watermelon (Citrullus lanatus) urease immobilized on VS2-chitosan nanocomposite beads using response surface methodology - Prince Kumar; Divya; Amit Kumar Patel; Anchal Srivastava; Arvind M. Kayastha (Food Chemistry, 2024)

Assessment of metals and metalloids agglutinated to airborne suspended particulate matter in selected plant species during the pre-and post-monsoon in the urban area - Durga Prasad Tripathi; Arvind Kumar Nema (Environmental Pollution, 2024)

Microsatellite polymorphism based genetic variation in two sympatric species of Drosophila: D. bipectinata and D. malerkotliana - Gurvachan Singh; Arvind Kumar Singh (Ecological Genetics and Genomics, 2024)

Construction of dual Z-scheme ternary carbon nitride homojunction pectin microspheres as a multifunctional photocatalyst for tetracycline degradation, H2O2 production, and N2 fixation - Akash Balakrishnan; Mahendra Chinthala; Arvind Kumar; Sami Rtimi (Chemical Engineering Journal, 2024)

5-Hydroxymethylfurfural and furfural synthesis from waste paper, cotton and poly/mono-meric carbohydrates - Rohit Bains; Arvind Singh Chauhan; Ajay Kumar; Mahender Kumar; Pralay Das (Biomass and Bioenergy, 2024)

Mapping Arsenic Contamination and Health Risk Assessment of Arsenic in Agricultural Soils of Eastern India - Rahul Mishra; Siba Prasad Datta; Debasis Golui; Mahesh Chand Meena; Md Basit Raza; Mohammad Mahmudur Rahman; Mahipal Chaudhary; Sanjib Kumar Behera; Amresh Chaudhary; Devi Prasad Upadhyay; Arvind Kumar Shukla (Water, Air, & Soil Pollution, 2024)

Enriched Environment Contributes to the Recovery from Neurotoxin-Induced Parkinson’s Disease Pathology - Daphne Alcalá-Zúniga; Erika Espinoza-Torres; Ranjit Kumar Das; Magaly Vargas; Oscar Maldonado; Omar Benavides; Arvind Manojkumar; Roberto de la Garza; Natalia Davila; Isaac Perez; Alejandro Hernandez Martinez; Deepa Roy; et al. (Molecular Neurobiology, 2024)
Parkinson’s disease (PD) is a neurological disorder that affects dopaminergic neurons. The lack of understanding of the underlying molecular mechanisms of PD pathology makes treating it a challenge. Several pieces of evidence support the protective role of enriched environment (EE) and exercise on dopaminergic neurons. The specific aspect(s) of neuroprotection after exposure to EE have not been identified. Therefore, we have investigated the protective role of EE on dopamine dysregulation and subsequent downregulation of DJ1 protein using in vitro and in vivo models of PD. Our study for the first time demonstrated that DJ1 expression has a direct correlation with dopamine downregulation in PD models and exposure to EE has a significant impact on improving the behavioral changes in PD mice. This research provides evidence that exercise in EE has a positive effect on PD without interfering with the current line of therapy.

PGPR-Mediated Breakthroughs in Plant Stress Tolerance for Sustainable Farming - Arun Karnwal; Seweta Shrivastava; Abdel Rahman Mohammad Said Al-Tawaha; Gaurav Kumar; Arvind Kumar; Anupam Kumar (Journal of Plant Growth Regulation, 2024)

Dissipation kinetics and the evaluation of dietary risks associated with deltamethrin, ethion, fenazaquin, and fenpropathrin on bell pepper (Solanum annuum L.) - Shubhra Singh; Jatiender Kumar Dubey; Sapna Katna; Ajay Sharma; Tanuja Banshtu; Nisha Devi; Gaganpreet Singh Brar; Gagandeep Singh; Arvind Kumar; Himani Gautam (Environmental Geochemistry and Health, 2024)

Optimization and Characterization of an Ultra-Thermostable, Acidophilic, Cellulase-Free Xylanase from a New Obligate Thermophilic Geobacillus thermoleovorans AKNT10 and its Application in Saccharification of Wheat Bran - Arvind Kumar; Tapati Bhanja Dey; Awdhesh Kumar Mishra; Khem Raj Meena; Himansu Sekhara Mohapatra; Ramesh Chander Kuhad (Current Microbiology, 2024)

Combatting synthetic dye toxicity through exploring the potential of lignin peroxidase from Pseudomonas fluorescence LiP RL5 - Ranju Kumari Rathour; Nidhi Rana; Vaishali Sharma; Nitish Sharma; Arvind Kumar Bhatt; Ravi Kant Bhatia (Environmental Science and Pollution Research, 2024)

PCA and fuzzy clustering-based delineation of soil nutrient (S, B, Zn, Mn, Fe, and Cu) management zones of sub-tropical Northeastern India for precision nutrient management - Arvind Kumar Shukla; Sanjib Kumar Behera; Anjali Basumatary; Indira Sarangthem; Rahul Mishra; Samiron Dutta; Yogesh Sikaniya; Akanksha Sikarwar; Vimal Shukla; Siba Prasad Datta (Journal of Environmental Management, 2024)

PMTPred: machine-learning-based prediction of protein methyltransferases using the composition of k-spaced amino acid pairs - Arvind Kumar Yadav; Pradeep Kumar Gupta; Tiratha Raj Singh (Molecular Diversity, 2024)

Conservation Agricultural Practices Influencing the Seasonal Weed Dynamic and Productivity of Wheat in the Trans Indo-Gangetic Plains of India - Seema Sepat; Arvind Kumar; Ramanjit Kaur; Harminder Singh; Bhagyashree Phogat; Dinesh Kumar; Rahul Sadhukhan; S. L. Meena; S. R. Choudhary; Ahmed Gaber; Akbar Hossain (Journal of Crop Health, 2024)

A Modified Anisotropic Hoek and Brown Failure Criterion for Transversely Isotropic Rocks - Gowtham Ganesan; Arvind Kumar Mishra (Geotechnical and Geological Engineering, 2024)

Computation of soil quality index after fifteen years of long-term tillage and residue management experiment (LT&RE) under rice wheat system - Ram K. Fagodiya; Gargi Sharma; Kamlesh Verma; Arvind Kumar Rai; Kailash Prajapat; Ranbir Singh; Priyanka Chandra; Parvender Sheoran; Rajender Kumar Yadav; A.K. Biswas (Agricultural Systems, 2024)

Winter convective mixing regulates oceanic C : N : P ratios - Deepika Sahoo; Himanshu Saxena; Sipai Nazirahmed; Mohammad Atif Khan; Deepak Kumar Rai; Niharika Sharma; Sebin John; Sanjeev Kumar; A. K. Sudheer; Ravi Bhushan; Arvind Singh (Limnology and Oceanography, 2024)
Recent studies have challenged the validity of the Redfield ratio. It is proposed that physical and biogeochemical processes govern the geographical variations in carbon : nitrogen : phosphorus (C : N : P) ratios. However, this proposal remains to be examined through concurrent observations of C : N : P ratios with physical and biogeochemical processes in various marine reservoirs. Here, we sampled the Arabian Sea for its C, N, and P content in organic and inorganic pools during the winter monsoon. We analyzed the role of convective mixing, eddies, and N 2 fixation to explain the variation in observed elemental ratios. Convective mixing injected the cold water and enhanced the supply of N and P nutrients in the top layer (surface to 50–75 m) of the northern Arabian Sea. This led to a decrease in the N : P and C : P ratios in the particulate organic matter in the northern region, but C : N : P increased equatorward, averaging 245 : 32 : 1 in the top layer of the Arabian Sea. The variation in the elemental ratios in the top layer is best explained by the changes in water temperature. N 2 fixation contributed negligibly to the N : P ratio of the export flux. The substantial decrease in N : P ratios of nutrients in the subsurface waters is most likely caused by the denitrifying conditions in the Arabian Sea. As the processes of convective mixing and eddies are are prevalent oceanic processes, our observations underpin that the interplay of these processes leads to changes in the elemental ratios globally.

Air pollution mitigation and suspended particulate matter retention potential of selected plant species across seasonal variation in the urban area - Durga Prasad Tripathi; Arvind Kumar Nema (Environmental Science and Pollution Research, 2024)

Millennial to centennial-scale climate oscillations since 15000 cal yrs BP from Kanwar wetland in the Central Ganga Plain, India - Binita Phartiyal; Arvind Tiwari; Masud Kawsar; Manoj M.C; Mayank Shekhar; S. Nawaz Ali; Ravi Bhushan; Rujal R. Pachchigar; Anurag Kumar; Prasanna K; Anupam Sharma (Quaternary Science Reviews, 2024)

A systematic review on assessment of heavy metals toxicity in freshwater fish species: Current scenario and remedial approaches - Arvind Kumar Sharma; Munish Sharma; Simran Sharma; Davendra Singh Malik; Munit Sharma; Munish Sharma; Amit Kumar Sharma (Journal of Geochemical Exploration, 2024)

Hypocholesterolemic potential of Bacillus amyloliquefaciens KAVK1 modulates lipid accumulation on 3T3-L1 adipose cells and high fat diet-induced obese rat model - V. Kokila; S. Karthick Raja Namasivayam; K. Amutha; R. Ramesh Kumar; R. S. Arvind Bharani; P. Surya (World Journal of Microbiology and Biotechnology, 2024)

Anthropogenic Impact on Habitat Ecology and Zooplankton Diversity in Ganges Riverine System Using Enviro Assessment Techniques - D. S. Malik; Arvind Kumar Sharma; Vishal Kamboj; Amit Kumar Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Proteome profile of nucleus accumbens (NAc) uncovers the differential and sex-specific role of CRMP2 in CVMS-induced mouse model of depression - Bhanu Chandra Karisetty; Divya Duscharla; Vincy Vijay; Shashikant Patel; Kalyani Soren; Arvind Kumar; Ramesh Ummanni; Sumana Chakravarty (Journal of Proteins and Proteomics, 2024)

Isolation and characterization of secondary metabolites from Bryophylum pinnatum (Lam.) Oken and assessment of wound healing efficacy using animal model - Harpreet Singh; Monika Singh; Sagnik Nag; Sourav Mohanto; Khushboo Jain; Alankar Shrivastav; Arun Kumar Mishra; Janardhan Pallavi; Adrija Bhunia; Vetriselvan Subramaniyan; Arvind Kumar; Amrita Mishra (South African Journal of Botany, 2024)

Assessment of functional efficacy of sheep plasma protein hydrolysates and their utilization in mutton sausage - Sarita Kumari; Anurag Pandey; Arvind Soni; Anurag Mahala; Arun Kumar; Kushankur Dey (Meat Science, 2024)

Immobilization of α-amylase onto functionalized molybdenum diselenide nanoflowers (MoSe2-NFs) as scaffolds: Characterization, kinetics, and potential applications in starch-based industries - Avinash Kumar; Ravi Dutt; Anchal Srivastava; Arvind M. Kayastha (Food Chemistry, 2024)

Molecular marker-assisted genetic diversity analysis in soybean cultivars from Himalayan region of Uttarakhand, India - Tina; Manu Pant; Kumud Pant; Akansha Chauhan; Arvind S. Negi; Pankaj Nainwal; Amrita Srivastava; Vijay Kumar (Ecological Genetics and Genomics, 2024)

A comprehensive study of palladium-based catalysts on different supports for the hydrogenolysis of 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF) biofuel - Arvind Singh Chauhan; Ajay Kumar; Rohit Bains; Mahender Kumar; Pralay Das (Biomass and Bioenergy, 2024)

Substitution of Inorganic Nitrogen with Organic Amendments for Improvement of Soil Properties, Microbial Community, and Enzymatic Activity in Maize-Wheat Cropping System Under Sub-temperate Ecology - Sukhchain Singh; Naveen Kumar; Sandeep Manuja; Pardeep Kumar; Sandeep; Sandeep Singh; Shwetansh; Arvind Chahal (Journal of Soil Science and Plant Nutrition, 2024)

Mining of rice rhizobacteria to control false smut and improve plant growth in rice (Oryza sativa L.) - Neha Pandey; Asha Singh Rajavat; Richa Vaishnav; Arvind Nath Singh; Sanjay Kumar; Vaibhav Mishra; Madan Kumar; Neeraj Shrivastava (European Journal of Plant Pathology, 2024)

Marine macro-litter sources and ecological impact: a review - Van-Giang Le; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Nguyen T. Quang Hung; Akhil P. Khedulkar; Nguyen K. Hue; Phung T. Thu Trang; Arvind Kumar Mungray; D. Duc Nguyen (Environmental Chemistry Letters, 2024)

Spatio-temporal trends in long-term seasonal groundwater level of South-western Punjab using non-parametric statistical tests - Arvind Dhaloiya; Jagdish Prasad Singh; Anurag Malik; Mahesh Chand Singh; Ajay Kumar (Environmental Science and Pollution Research, 2024)

Combined electrical resistivity tomography and high-resolution shallow seismic analysis for coal exploration in Talcher Coalfield, India - Arvind Yadav; Thinesh Kumar; Anurag Tripathi; Sanjit Kumar Pal; Shalivahan (Acta Geophysica, 2024)

Effect of boron fertilization on productivity and sustainability of rice-wheat cropping system in Tarai region, North-West India - S.P. Pachauri; Arvind K. Shukla; P.C. Srivastava; Sanjib K. Behara; Nagender Pal Butail; Pratibha Thakur; Praveen Thakur; Anjali; Munish Sharma; Pradeep K. Sharma; Ankita Sahu; Pardeep Kumar (Journal of Environmental Management, 2024)

Financial well-being of women self-help group members: a qualitative study - Barun Srivastava; Vinay Kandpal; Arvind Kumar Jain (Environment, Development and Sustainability, 2024)

Machine learning-based design and monitoring of algae blooms: Recent trends and future perspectives – A short review - Abdul Gaffar Sheik; Arvind Kumar; Reeza Patnaik; Sheena Kumari; Faizal Bux (Critical Reviews in Environmental Science and Technology, 2024)

A hybrid metaheuristic approach to solve grid centric cleaner economic energy management of microgrid systems - Bishwajit Dey; Srikant Misra; Tapas Chhualsingh; Akshya Kumar Sahoo; Arvind R. Singh (Journal of Cleaner Production, 2024)

Sequential submergence and drought induce yield loss in rice by affecting redox homeostasis and source-to-sink sugar transport - Santosh Kumar; Sahana Basu; A.K. Choudhary; Shashi Shekhar; J.S. Mishra; Sanjeev Kumar; Kumari Shubha; Rachana Dubey; Surajit Mondal; S.K. Dwivedi; N. Bhakta; Rakesh Kumar; et al. (Field Crops Research, 2024)

A Generalized Failure Mode Model for Transversely Isotropic Rocks Using a Machine Learning Classification Approach - Gowtham Ganesan; Arvind Kumar Mishra; K. Mathanlal (Rock Mechanics and Rock Engineering, 2024)

Overexpression of the chickpea Metallothionein 1 (MT1) gene enhances drought tolerance in mustard (Brassica juncea L.) - Swati Lal; Varun Kumar; Uma Gupta; Sushma; Pramod Arvind Shirke; Indraneel Sanyal (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Identification of earthquake induced structural damage based on synchroextracting transform - Kumar Roshan; Kumar Gaurav; Zhao Wei; Arvind R. Yadav; Yu Gang; Jayendra Kumar; Evans Amponsah (Earthquake Engineering and Engineering Vibration, 2024)

Residue behavior and consumer risk assessment of spirotetramat and chlorpyrifos on cabbage heads and cropped soil - Pankaj Sharma Istatu; Jatiender Kumar Dubey; Sapna Katna; Ajay Sharma; Sakshi Sharma; Deepika Shandil; Nisha Devi; Arvind Kumar; Shubhra Singh; Nimisha Thakur (Environmental Science and Pollution Research, 2024)

Pollution fingerprintings in soils and plants of Buddha Nalah drain contaminated with industrial effluents - Salwinder Singh Dhaliwal; Vivek Sharma; Janpriya Kaur; Arvind Kumar Shukla; Vibha Verma; Jaswinder Singh; Manmeet Kaur; Prabhjot Singh (Environment, Development and Sustainability, 2024)

Effect of various chemical solutions on micropropagation efficiency, antioxidant activities and clonal fidelity analysis of in vitro developed plantlets in pomegranate (Punica granatum L.) using SSR markers - Devendra Pal; Mukesh Kumar; Manoj Kumar Yadav; Chetan Chauhan; Arvind Kumar; Ujjwal Sirohi; V. Rakesh Sharma; Veena Chaudhary (Vegetos, 2024)

In vitro plant regeneration, genetic fidelity, biochemical analysis and anticancer activity of anthocyanin-rich purple flesh sweet potato var. ‘Bhu Krishna’ - Shashikanta Behera; Vijay Bahadur Singh Chauhan; Kumari Monalisa; Rajesh K. Meher; Subrat K. Kar; Kalidas Pati; Venkatraman V. Bansode; M. Nedunchezhiyan; Arvind Kumar Verma; Pradeep K. Naik; Soumendra K. Naik (South African Journal of Botany, 2024)

Uncovering Sex-Specific Epigenetic Regulatory Mechanism Involving H3k9me2 in Neural Inflammation, Damage, and Recovery in the Internal Carotid Artery Occlusion Mouse Model - Mydhili Radhakrishnan; Vincy Vijay; B. Supraja Acharya; Papia Basuthakur; Shashikant Patel; Kalyani Soren; Arvind Kumar; Sumana Chakravarty (NeuroMolecular Medicine, 2024)

A review of microbial fuel cell and its diversification in the development of green energy technology - Amol V. Sonawane; Satish Rikame; Shirish H. Sonawane; Mahendra Gaikwad; Bharat Bhanvase; Shriram S. Sonawane; Arvind Kumar Mungray; Ravindra Gaikwad (Chemosphere, 2024)

Vermiculite nanosheet augmented novel proton exchange membrane for microbial fuel cell - Parini Surti; Suresh Kumar Kailasa; Alka Mungray; Tae Jung Park; Arvind Kumar Mungray (Fuel, 2024)

Synergetic oxidative esterification of 5-hydroxymethylfurfural using Pd-Au bimetallic nanocomposite under mild conditions - Ajay Kumar; Arvind Singh Chauhan; Rohit Bains; Pralay Das (Chemical Engineering Journal, 2024)

Recent immobilization techniques for ketoreductases: Its design and their industrial application - Prabha Kumari; Amol G. Khatik; Pravin D. Patil; Manishkumar S. Tiwari; Shamraja S. Nadar; Arvind Kumar Jain (Biocatalysis and Agricultural Biotechnology, 2024)

Degradation and metagenomic analysis of 4-chlorophenol utilizing multiple metal tolerant bacterial consortium - Lhinglamkim Kipgen; Ningombam Anjana Singha; Waniabha J. Lyngdoh; Jopthiaw Nongdhar; Arvind Kumar Singh (World Journal of Microbiology and Biotechnology, 2024)

Evaluating Environmental Impacts: A Comprehensive Investigation of Sugarcane-Based Bioethanol Production in Northwest Region of India - Rohit Kumar; Arvind Bhardwaj; Lakhwinder Pal Singh (Sugar Tech, 2024)

Overexpressing the glutaredoxin (CaGrx) gene enhances the antioxidant defences and improves drought tolerance in chickpea (Cicer arietinum L.) - Varun Kumar; Anil Kumar; Meenakshi; Uma Gupta; Shiv Narayan; Pramod Arvind Shirke; Indraneel Sanyal (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Development of a directional continuous joint adjustment rating for the rock mass rating system - Gowtham Ganesan; Arvind Kumar Mishra (Arabian Journal of Geosciences, 2024)

Methodological Breakdown of Potato Peel’s Influence on Starch Digestibility, In Vitro Glycemic Response and Pasting Properties of Potato - Milan Kumar Lal; Rahul Kumar Tiwari; Awadhesh Kumar; Ravinder Kumar; Dharmendra Kumar; Arvind Jaiswal; Sushil Sudhakar Changan; Som Dutt; Jelena Popović-Djordjević; Brajesh Singh; Jesus Simal-Gandara (American Journal of Potato Research, 2024)
A Potato ( Solanum tuberosum L.) is a major staple food consumed worldwide. Potato peel is an important constituent that is generally discarded and considered agricultural waste before processing or cooking. The present investigation is an attempt to utilize different contents of potato peels (PP) with potato flesh (PF) of processing cultivar (Kufri Chipsona 3) and table cultivar (Kufri Jyoti), which affect starch nutritional profile, glycemic response, and pasting properties. The combination of PP at different concentrations of 5, 10, and 15%, respectively, to PF showed a significant reduction ( P

Residue estimation and dietary risk assessment of fenvalerate, novaluron, and profenofos in bell pepper grown under protected and open field conditions - Himani Gautam; Sapna Katna; Jatiender Kumar Dubey; Ajay Sharma; Gaganpreet Singh Brar; Shubhra Singh; Nisha Devi; Arvind Kumar; Hema Prashad (Environmental Science and Pollution Research, 2024)

Bridging gaps in the Indian freshwater biodiversity conservation through science-based and policy-backed recommendations - Kritish De; Arvind Kumar Dwivedi (Ecohydrology & Hydrobiology, 2024)

CstMYB1R1, a REVEILLE-8-like transcription factor, regulates diurnal clock-specific anthocyanin biosynthesis and response to abiotic stress in Crocus sativus L - Zahid Yaqoob Bhat; Javid Ahmad Mir; Arvind Kumar Yadav; Deepika Singh; Nasheeman Ashraf (Plant Cell Reports, 2024)

The key genomic regions harboring QTLs associated with salinity tolerance in bread wheat (Triticum aestivum L.): a comprehensive review - Shiksha Chaurasia; Arvind Kumar (Journal of Crop Science and Biotechnology, 2024)

Residue behaviour and health risk assessment of chlorpyrifos and mancozeb in apple fruits and soil - Ajay Sharma; Sapna Katna; Jatiender Kumar Dubey; Sakshi Sharma; Pankaj Sharma Istatu; Nisha Devi; Gaganpreet Singh Brar; Arvind Kumar; Shubhra Singh; Hema Prashad (Environmental Monitoring and Assessment, 2024)

Use of machine learning-based classification algorithms in the monitoring of Land Use and Land Cover practices in a hilly terrain - Deepanshu Parashar; Ashwani Kumar; Sarita Palni; Arvind Pandey; Anjaney Singh; Ajit Pratap Singh (Environmental Monitoring and Assessment, 2024)

Mapping the impact of environmental pollutants on human health and environment: A systematic review and meta-analysis - Amit Kumar Sharma; Munish Sharma; Arvind Kumar Sharma; Munit Sharma; Munish Sharma (Journal of Geochemical Exploration, 2023)

Ultrasound-induced PMS activation for acrylonitrile degradation with series LTZ perovskite-like catalysts: Synergistic and mechanistic insight - Arvind Kumar; Abdul Gaffar Sheik; Basheswar Prasad; Sheena Kumari; Faizal Bux (Journal of Environmental Chemical Engineering, 2023)

Quantifying ecological impacts: A comparative life cycle assessment of conventional and organic potato cultivation - Rohit Kumar; Arvind Bhardwaj; Lakhwinder Pal Singh; Gurraj Singh (Ecological Modelling, 2023)

Converting waste to resource: Utilisation of elemental S and consortia of halo–alkaliphilic S–oxidisers for preparation of acidified compost from organic wastes - Sandeep Bedwal; Nirmalendu Basak; Arvind Kumar Rai; Parul Sundha; Subedar Patel; Dev Raj; Anita Mann; Sanjay Kumar; Priyanka Chandra; Rajender Kumar Yadav (Bioresource Technology Reports, 2023)

Nitrogen dose dependant changes in grain morphology parameters are correlated with grain protein and yield traits in field-grown diverse rice genotypes - Birendra K. Padhan; Lekshmy Sathee; Santosh Kumar; Manoranjan Senapati; Viswanathan Chinnusamy; S. Gopala Krishnan; Dinesh Kumar; Navin Chandra Gupta; Arvind Kumar (Plant Physiology Reports, 2023)

Muscle Transcriptome Sequencing Revealed Thermal Stress–Responsive Regulatory Genes in Farmed Rohu, Labeo rohita (Hamilton, 1822) - Pokanti Vinay Kumar; Kiran D. Rasal; Arpit Acharya; Diganta Dey; Arvind A. Sonwane; Dhalongsaih Reang; R. Rajeshkannan; Sachin S. Pawar; Nitin P. Kurade; Mukesh P. Bhendarkar; Kishore K. Krishnani; Naresh S. Nagpure; et al. (Marine Biotechnology, 2023)

Exploration of Cd transformations in Cd spiked and EDTA-chelated soil for phytoextraction by Brassica species - Salwinder Singh Dhaliwal; Vivek Sharma; Arvind Kumar Shukla; Parminder Kaur Taneja; Lovedeep Kaur; Vibha Verma; Manmeet Kaur; Janpriya Kaur (Environmental Geochemistry and Health, 2023)

Production and quality of Napier bajra hybrid (Pennisetum purpureum × Pennisetum americanum) in Eucalyptus tereticornis based silvi-pastoral system - Naveen Kumar; Arvind Chahal; S. R. Kantwa; Gurudev Singh; Sukhchain Singh (Agroforestry Systems, 2023)

The underpinning factors affecting the classroom air quality, thermal comfort and ventilation in 30 classrooms of primary schools in London - Sarkawt Hama; Prashant Kumar; Arvind Tiwari; Yan Wang; Paul F. Linden (Environmental Research, 2023)

Carbon capture from petrol-engine flue gas: Reviving algae-based sequestration with integrated microbial fuel cells - Arti Sharma; Prasenjit Sarkar; Meenu Chhabra; Ajay Kumar; Arvind Kumar; Hardik Kothadia; Ayan Mallick (Chemical Engineering Journal, 2023)

3D black g-C3N4 isotype heterojunction hydrogels as a sustainable photocatalyst for tetracycline degradation and H2O2 production - Akash Balakrishnan; Emmanuel Sebastian Kunnel; Roshini Sasidharan; Mahendra Chinthala; Arvind Kumar (Chemical Engineering Journal, 2023)

Characteristics of atmospheric boundary layer structure using monostatic SODAR system over Mumbai region - Nishant Kumar; Anjali S Nair; Kirti Soni; A A Shingare; Vidyanand M Motghare; Karansingh A Rajput; V K Soni; Anikender Kumar; Arvind Kumar Jha (Journal of Earth System Science, 2023)

Bacillus velezensis strain improvement to control Helminthosporium maydis causing southern corn leaf blight disease in maize - Vahida Rahman; Khem Raj Meena; Laith Khalil Tawfeeq Al-Ani; Ashutosh Singh; Arvind Kumar (European Journal of Plant Pathology, 2023)

Immunotoxicity of cynobacterial toxin Microcystin-LR is mitigated by Quercitin and himalaya tonic Liv52 - Kriti Shrinet; Arvind Kumar (Toxicon, 2023)

Understanding the role of surface runoff in potential flood inundation in the Kashmir valley, Western Himalayas - Tauseef Ahmad; Arvind Chandra Pandey; Amit Kumar; Anamika Tirkey (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Quantitative NMR external standard fit-for-purpose method for fluorine-containing compounds: Expanding the application of aSSICO signal method to 19F nuclei - Hemantha Kumar; Felix Kulandai; Naga Durga Harish Ravuri; Mitalee Das; Amrita Roy; Arvind Mathur; Janet Caceres-Cortes (Journal of Fluorine Chemistry, 2023)

Consumer preference for nutrition front-of-pack-label formats in India: Evidence from a large-scale experimental survey - Ranjan Kumar Ghosh; Rahul Sanghvi; Arvind Sahay (Food Quality and Preference, 2023)

Development of tailored bioprocess for pretreatment and saccharification of corn stalk into bioethanol using hydrolytic enzymes cocktail and fermentative yeasts - Manya Behl; Pushpak Dahiya; Deeksha Kumari; Kalpana Thakur; Mamta Devi; Ranju Kumari Rathour; Arvind Kumar Bhatt; Ravi Kant Bhatia (Biocatalysis and Agricultural Biotechnology, 2023)

Reducing Arsenic Uptake in Cereal Crop Plants with Sugarcane Waste Application: A Comparative Study on the Effects on Physiology, Biochemistry, and Grain Nutrient Status - Ambedkar Gautam; Nikita Basant; Navin Kumar; Kriti; Shiv Naresh Singh; Arvind Kumar Dubey; Gayatri Singh; Babita Kumari; Kavita Shah; Shekhar Mallick (Journal of Plant Growth Regulation, 2023)

Dynamics of environmental variables during the incidence of algal bloom in the coastal waters of Gujarat along the northeastern Arabian Sea - Vinaya Kumar Vase; Mini Raman; Arvind Sahay; Shikha R.; Rajan K.; Sreenath K.R.; Gyanaranjan Dash; Jayasankar J.; Prathibha Rohit; Ratheesh Kumar R. (Environmental Monitoring and Assessment, 2023)

Effect of mini-sprinkler irrigation, tillage and residue on productivity, profitability and resource saving in rice–wheat system in western Indo-Gangetic Plains of India - Ranbir Singh; Ajay Singh; Satyendra Kumar; Ram K. Fagodiya; Parvender Sheoran; Arvind Kumar Rai; Sonia Rani; Priyanka Chandra (Paddy and Water Environment, 2023)

Statistical modelling of the blast design parameters influencing ground vibrations in a limestone quarry using design-expert - Balamadeswaran Periasamy; Arvind Kumar Mishra (Arabian Journal of Geosciences, 2023)

Link of the short-term temporal trends of Sr and Nd isotopic composition of aeolian dust over the Arabian Sea with the source emissions - Srinivas Bikkina; Arvind Shukla; Sunil Kumar Singh; Damodaraorao Karri; Naman Deep Singh; Bisweswar Sahoo (Science of The Total Environment, 2023)

Seasonal variation of biochemical parameters and air pollution tolerance index (APTI) of selected plant species in Delhi city, and detailed meta-analysis from Indian metropolitan cities - Durga Prasad Tripathi; Arvind Kumar Nema (Atmospheric Environment, 2023)

Morphological, phytochemical, and transcriptome analyses provide insights into the biosynthesis of monoterpenes in Monarda citriodora - Priyanka Sharma; Mir Abdul Wajid; Mohd Fayaz; Sheetal Bhat; Abhishek Kumar Nautiyal; Sabha Jeet; Arvind Kumar Yadav; Deepika Singh; Ravi Shankar; Sumeet Gairola; Prashant Misra (Planta, 2023)

Arsenic Cleanup Goals in Soil-Water-Rice-Human Continuum: Interplay of Amendments - Rubina Khanam; Gora Chand Hazra; Pedda Ghouse Peera Sheikh Kulsum; Nitin Chatterjee; Umalaxmi Thingujam; Arvind Kumar Shukla (Journal of Soil Science and Plant Nutrition, 2023)

Harnessing the action mechanisms of microbial endophytes for enhancing plant performance and stress tolerance: current understanding and future perspectives - Gursharan Kaur; Arvind Patel; Vagish Dwibedi; Santosh Kumar Rath (Archives of Microbiology, 2023)

Mutation spectrum and enzyme profiling of G6PD deficiency in neonates of north India: a prospective study - Upasana Bhattacharyya; Preeti Deswal; Sunil Kumar Polipalli; Diksha Sharma; Manpreet Kaur; Madhulika Kabra; Neerja Gupta; Ramesh Agarwal; A. K. Deorari; V. K. Paul; Shevendru Roy; R. K. Sanjeev; et al. (Journal of Genetics, 2023)

A better understanding of Archean crustal evolution: exploring the sedimentary archive of the Singhbhum Craton, eastern India - Arvind Kumar Gond; Sukanta Dey; Keqing Zong; Yongsheng Liu; R. Anand; Anirban Mitra; Aniruddha Mitra (Journal of Asian Earth Sciences, 2023)

Noteworthy biocompatibility of effective microorganisms (EM) like microbial beneficial culture formulation with metal and metal oxide nanoparticles - S. Karthick Raja Namasivayam; Sharvan Kumar; K. Samrat; R.S. Arvind Bharani (Environmental Research, 2023)

Proximate composition and mineral content analysis of Curcuma caesia rhizome - Arvind Kumar Bhardwaj; Nand Kumar Kashyap; Sanjoy Kumar Bera; Milan Hait; Harishankar Dewangan (Biochemical Systematics and Ecology, 2023)

Tensile strength of cemented paste backfill for lead–zinc mill tailings: lab and in situ scenarios - Santosh Kumar Behera; Devi Prasad Mishra; Prashant Singh; Ashok Godugu; Kanhaiya Mishra; Phanil Kumar Mandal; Sujit Kumar Mandal; Arvind Kumar Mishra (Arabian Journal of Geosciences, 2023)

Evaluation of growth, yield, economics and soil properties of agri-horticulture systems in mid-hill situations of Himalayas - Abhishek Pratap Singh; Arvind Bijalwan; Tejpal Singh Bisht; Bhupendra Singh; Sandeep Kumar; Naveen Tariyal (Agroforestry Systems, 2023)

Valorised polypropylene waste based reversible sensor for copper ion detection in blood and water - Sweety Rani; Ishana Kathuria; Arvind Kumar; Dheeraj Kumar; Advitiya Kumar; Satish Kumar; Bhanu Nandan; Rajiv K. Srivastava (Environmental Research, 2023)

Enhanced flushing in long emergent vegetation with two flow parallel interfaces: simulation and predictive modeling at moderate Reynolds number - Arvind Kumar Bairwa; Rakesh Khosa; Maheswaran Rathinasamy (Stochastic Environmental Research and Risk Assessment, 2023)

Estimation Equations for Back Break and Ground Vibration Using Genetic Programming - Shankar Kumar; Arvind Kumar Mishra; Bhanwar Singh Choudhary (Geotechnical and Geological Engineering, 2023)

Performance analysis of a serrated absorber plate solar air heater with paraffin wax storage - Arvind Kumar Singh; Abhishek Saxena; Nitin Agarwal (Environmental Science and Pollution Research, 2023)

Matching N supply for yield maximization in salt–affected wheat agri–food systems: On-farm participatory assessment and validation - Parvender Sheoran; Paras Kamboj; Arvind Kumar; Ashwani Kumar; Ranjay K. Singh; Arijit Barman; Kailash Prajapat; Subhasis Mandal; Dar Jaffer Yousuf; Bhaskar Narjary; Satyendra Kumar (Science of The Total Environment, 2023)

Reduction of arsenic accumulation in rice grain by endophytic fungus Serendipita indica - Jagriti Shukla; Shiv Narayan; Aradhana Mishra; Pramod Arvind Shirke; Manoj Kumar (Rhizosphere, 2023)

Carbon and water footprints of major crop production in India - Amaresh Kumar NAYAK; Rahul TRIPATHI; Manish DEBNATH; Chinmaya Kumar SWAIN; Biswaranjan DHAL; Shanmugam VIJAYKUMAR; Anshuman Debasis NAYAK; Sangita MOHANTY; Mohammad SHAHID; Anjani KUMAR; Manoj RAJAK; Khitish Chandra MOHARANA; et al. (Pedosphere, 2023)

Reduced graphene oxide-nano zerovalent iron assisted anaerobic digestion of dairy wastewater: A potential strategy for CH4 enrichment - Roshini Sasidharan; Arvind Kumar; Balasubramanian Paramasivan; Abanti Sahoo (Journal of Environmental Chemical Engineering, 2023)

Functional bagasse: As a versatile catalyst for henry reaction and additive-free cycloaddition of CO2 - Krishnan Ravi; Jean-Louis K. GBE; Sanjay Mehra; Srinu Tothadi; Arvind Kumar; Ankush V. Biradar (Journal of Environmental Chemical Engineering, 2023)

Reference genes for expression studies in different developmental stages of Oryctes rhinoceros, the coconut rhinoceros beetle - Kumar Arvind; Ginny Antony; M.K. Rajesh; A. Josephrajkumar; Tony Grace (Journal of Asia-Pacific Entomology, 2023)

Spatio-temporal variability of available sulphur and micronutrients (Zn, Fe, Cu, Mn, B and Mo) in soils of a hilly region of northern India - Sanjib Kumar Behera; Arvind Kumar Shukla; Satya Pratap Pachauri; Vimal Shukla; Yogesh Sikaniya; Prakash Chandra Srivastava (CATENA, 2023)

Analysis of Behaviour of Caverns with Varying Pillar Widths Between the Caverns - Anant Kumar Shukla; Arvind Kumar Mishra; Tanwee Mazumder; G. Doraswamy Raju (Geotechnical and Geological Engineering, 2023)

Unique Geosites around Zawar, Rajasthan, Western India: Its Linkage with Ancient Mining-Metallurgy and Archaeological Geodiversity - Arvind Kumar; P. R. Golani (Geoheritage, 2023)

Spatial variability of soil properties and delineation of management zones for Suketi basin, Himachal Himalaya, India - Praveen Kumar; Munish Sharma; Nagender Pal Butail; Arvind Kumar Shukla; Pardeep Kumar (Environment, Development and Sustainability, 2023)

Influence of Wetting-Drying Cycles on Strength Behaviour of Cured Lime Treated Soil Contaminated with Monovalent and Divalent Sulphatic Solutions - Shivanshi; Arvind Kumar Jha; Mohammad Parwez Akhtar (Transportation Geotechnics, 2023)

Modern biotic and abiotic analogues from the surface soil of Ganga-Ghaghara-Gandak interfluves of the Central Ganga Plain (CGP), India: Implications for the palaeoecological reconstructions - Swati Tripathi; Biswajeet Thakur; Anupam Sharma; Binita Phartiyal; Sadhan Kumar Basumatary; Ruby Ghosh; Kamlesh Kumar; M.C. Manoj; Shailesh Agrawal; Anjum Farooqui; Pooja Tiwari; Korobi Saikia; et al. (CATENA, 2023)

A pathway for multi-stage cyclone-induced hazard tracking—case study for Yaas - Atul Kumar Varma; Neeru Jaiswal; Ayan Das; Mukesh Kumar; Nikhil V. Lele; Rojalin Tripathy; Saroj Maity; Mehul Pandya; Bimal Bhattacharya; Anup Kumar Mandal; M. Jishad; M. Seemanth; et al. (Natural Hazards, 2023)

Photocatalytic pretreatment of dairy wastewater and benefits of the photocatalyst as an enhancer of anaerobic digestion - Roshini Sasidharan; Arvind Kumar; Balasubramanian Paramasivan; Abanti Sahoo (Journal of Water Process Engineering, 2023)

Aquatic biomass cellulose fabrication into cellulose nanocomposite and its application in water purification - S. Karthick Raja Namasivayam; P. Prakash; Vishnupriya Babu; Eric Johnson Paul; R.S. Arvind Bharani; J. Aravind Kumar; M. Kavisri; Meivelu Moovendhan (Journal of Cleaner Production, 2023)

Precambrian tectonics and metacratonization in the NW Indian shield inferred from magnetotelluric imaging across the Marwar Terrane and Aravalli-Delhi Mobile Belt - Abdul Azeez Kizhakkekara Kunjavaran; Veeraswamy Koppireddy; Prasanta Kumar Patro; Arvind Kumar Gupta; Narendra Babu (Journal of Asian Earth Sciences, 2023)

Accumulation of Cadmium in Transplanted Lichen Pyxine cocoes (Sw.) Nyl., with Reference to Physiochemical Variation and Kinetics of Cadmium Biosorption - Bushra Khatoon Ansari; Arvind Kumar Shukla; Dalip Kumar Upreti; Rajesh Bajpai (Bulletin of Environmental Contamination and Toxicology, 2023)

Jute and kenaf carrier bags: an eco-friendly alternative to plastic bags in India - Arvind Kumar Singh; Shamna Aboo; Tinku Goswami; Gouranga Kar (Environmental Science and Pollution Research, 2023)

Experimental and numerical analysis of the under-reamed piled ring foundation - Prince Karandeep Singh Sandhu; Arvind Kumar (Marine Georesources & Geotechnology, 2023)

A foam column system harvesting freshwater algae for biodiesel production: An experiment and process model evaluations - Shurooq T. Al-Humairi; Jonathan G.M. Lee; Adam P. Harvey; Ali Dawood Salman; Tatjána Juzsakova; B. Van; Phuoc–Cuong Le; D. Duong La; Arvind Kumar Mungray; Pau Loke Show; D. Duc Nguyen (Science of The Total Environment, 2023)

Rhizobacteria improve rice zinc nutrition in deficient soils - Awtar Singh; Shailja Mishra; Madhu Choudhary; Priyanka Chandra; Arvind Kumar Rai; Rajender Kumar Yadav; Parbodh Chander Sharma (Rhizosphere, 2023)

Sustainable approach to manage the vulnerable rodents using eco-friendly green rodenticides formulation through nanotechnology principles – A review - S. Karthick Raja Namasivayam; Subramanian Srinivasan; Krishnappa Samrat; Bala Priyalakshmi; Ramkumar Dinesh Kumar; Arvind Bharani; Ramkumar Ganesh Kumar; M. Kavisri; Meivelu Moovendhan (Process Safety and Environmental Protection, 2023)

The Himalayas: A climate change laboratory - Harsh Kumar Chauhan; David Gallacher; Arvind Bhatt; Anil Kumar Bisht (Environmental Development, 2023)

Post-Harvest Losses in Potatoes from Farm to Fork - Arvind Kumar Jaiswal; Brajesh Singh; Ashiv Mehta; Milan Lal (Potato Research, 2023)

Quantitative, Qualitative, and Energy Assessment of Boron Fertilization on Maize Production in North-West Himalayan Region - Pratibha Thakur; Pardeep Kumar; Arvind Kumar Shukla; Nagender Pal Butail; Munish Sharma; Praveen Kumar; Upinder Sharma (International Journal of Plant Production, 2023)

A Study on Dunaliella salina Under Selected Nutrient Manipulation with Reference to the Biomass, Lipid Content Along with Expression of ACCase and RuBisCO Genes - Sk Riyazat Khadim; Abhishek Mohanta; Prabhakar Singh; Priyanka Maurya; Ankit Kumar Singh; Arvind Kumar Singh; Ravi Kumar Asthana (BioEnergy Research, 2023)

Enhancement of electrode properties using carbon dots functionalized magnetite nanoparticles for azo dye decolorization in microbial fuel cell - Parini Surti; Suresh Kumar Kailasa; Arvind Kumar Mungray (Chemosphere, 2023)

The food-energy-water-carbon nexus of the rice-wheat production system in the western Indo-Gangetic Plain of India: An impact of irrigation system, conservational tillage and residue management - Ram K. Fagodiya; Ajay Singh; Ranbir Singh; Sonia Rani; S. Kumar; Arvind Kumar Rai; Parvender Sheoran; Priyanka Chandra; R.K. Yadav; P.C. Sharma; A.K. Biswas; S.K. Chaudhari (Science of The Total Environment, 2023)

Convective mixing and transport of the Bay of Bengal water stir the δ18O-salinity relation in the Arabian Sea - P. Kiran Kumar; Arvind Singh; R. Ramesh (Journal of Marine Systems, 2023)

Hydrothermal carbonization of cow dung with human urine as a solvent for hydrochar: An experimental and kinetic study - Zavin R. Gajera; Alka A. Mungray; Eldon R. Rene; Arvind Kumar Mungray (Journal of Environmental Management, 2023)

Modeling and prediction of fire occurrences along an elevational gradient in Western Himalayas - Somnath Bar; Bikash Ranjan Parida; Arvind Chandra Pandey; B. Uma Shankar; Pankaj Kumar; Santosh K. Panda; Mukunda Dev Behera (Applied Geography, 2023)

Scalable architecture of low-cost household microbial fuel cell for domestic wastewater treatment and simultaneous energy recovery - Jain Suransh; Dipak A. Jadhav; D. Duc Nguyen; Arvind Kumar Mungray (Science of The Total Environment, 2023)

Evaluating biochemical and biophysical characteristics of tropical deciduous forests of eastern India using remote sensing and in-situ parameter estimation - Arvind Chandra Pandey; Neha Kumari; Shahbaz Ahmad; Amit Kumar; Purabi Saikia; Bikash Parida; Satendra Kumar Chaudhary; Nikhil Lele (Remote Sensing Applications: Society and Environment, 2023)

Gamma (γ)-radiation stress response of the cyanobacterium Anabaena sp. PCC7120: Regulatory role of LexA and photophysiological changes - Akanksha Srivastava; Arvind Kumar; Subhankar Biswas; Rajender Kumar; Vaibhav Srivastava; Hema Rajaram; Yogesh Mishra (Plant Science, 2023)

Micro-characteristics of a naturally ventilated classroom air quality under varying air purifier placements - Prashant Kumar; Nidhi Rawat; Arvind Tiwari (Environmental Research, 2023)

Irrigation water quality, gypsum, and city waste compost addition affect P dynamics in saline-sodic soils - Parul Sundha; Nirmalendu Basak; Arvind Kumar Rai; Rajender Kumar Yadav; Parbodh Chander Sharma (Environmental Research, 2023)

Insights into the presence of multiple RecQ helicases in the ancient cyanobacterium, Nostoc sp. strain PCC7120: bioinformatics and expression analysis approach - Arvind Kumar; Hema Rajaram (Molecular Genetics and Genomics, 2023)

Magnitude and determinants of energy intensity: evidence from Indian firms - Aman Kumar; Arvind Mittal; Ashis Kumar Pradhan (Environmental Science and Pollution Research, 2023)

Modeling the effect of unemployment augmented industrialization on the control of unemployment - Pushkar Kumar Singh; Kusum Lata; Arvind Kumar Singh; Arvind Kumar Misra (Environment, Development and Sustainability, 2023)

Exploring variation in the fecal microbial communities of Kasaragod Dwarf and Holstein crossbred cattle - M Deepthi; Kumar Arvind; Rituja Saxena; Joby Pulikkan; Vineet K. Sharma; Tony Grace (Antonie van Leeuwenhoek, 2023)

Performance evaluation of deep eutectic solvent as a draw solute and vertical up-flow forward osmosis module for desalination of seawater - Sristina Baruah; Asfak Patel; Arvind Kumar Mungray; Alka A. Mungray (Environmental Science and Pollution Research, 2022)

Nutritional, Processing and Sensorial Attributes of Organic and Inorganic Indian Potatoes - Pinky Raigond; Sanjay Rawal; Vandana Parmar; Asha Thakur; Bandana; Tanuja Mishra; Som Dutt; Arvind Jaiswal; Milan Kumar Lal; Sushil S. Changan; Dharmendra Kumar; Brajesh Singh (Potato Research, 2022)

Behavior of eccentrically and obliquely loaded ring footing resting on geocell-reinforced sand - Vaibhav Sharma; Arvind Kumar (Innovative Infrastructure Solutions, 2022)

Impact of climate on vegetation in Pindari watershed of Western Himalayas, Kumaun, India, using spatiotemporal analysis: 1972–2018 - Arvind Pandey; Deepanshu Parashar; Naveen Chandra Bhatt; Sarita Palni; Charu Pundir; Arvind Singh Yadav; Ajit Pratap Singh; Pankaj Kumar Bhatt (Environmental Science and Pollution Research, 2022)

Multiplex PCR assay for the detection of Lr24 and Lr68 in salt tolerant wheat genotypes - Charu Lata; Arvind Kumar; O. P. Gangwar; Pramod Prasad; Sneha Adhikari; Subodh Kumar; Neeraj Kulshreshtha; S. C. Bhardwaj (Cereal Research Communications, 2022)

Forest Fire Characterization Using Landsat-8 Satellite Data in Dalma Wildlife Sanctuary - Satendra Kumar Chaudhary; Arvind Chandra Pandey; Bikash Ranjan Parida (Remote Sensing in Earth Systems Sciences, 2022)

Impact of Gd3+ doping on structural, electronic, magnetic, and photocatalytic properties of MnFe2O4 nanoferrites and application in dye-polluted wastewater remediation - Arvind Kumar; Mahendra Kumar Gora; Ganesh Lal; Banwari Lal Choudhary; Parmeshwar Lal Meena; Rajendra Singh Dhaka; Rishi Kumar Singhal; Sudhish Kumar; Satya Narain Dolia (Environmental Science and Pollution Research, 2022)

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sampa Sarkar; Sagar Swami; Sarvesh Kumar Soni; Jessica K. Holien; Arshad Khan; Arvind M. Korwar; Anjali P. Likhite; Ramesh A. Joshi; Rohini R. Joshi; Dhiman Sarkar (Molecular Diversity, 2022)

Electronic, optical and magnetic properties of Cu-doped ZnO, a possible system for eco-friendly and energy-efficient spintronic applications - Mahendra Kumar Gora; Arvind Kumar; Sanjay Kumar; Pankaj Kumar Maheshwari; Dinesh patidar; Satya Narain Dolia; Rishi Kumar Singhal (Environmental Science and Pollution Research, 2022)

Using geoinformatics to link forest fire severity and fragmentation in India's Dalma Wildlife Sanctuary - Satendra Kumar Chaudhary; Arvind Chandra Pandey; Bikash Ranjan Parida; Saurabh Kumar Gupta (Tropical Ecology, 2022)

Primary productivity estimation of forest based on in-situ biophysical parameters and sentinel satellite data using vegetation photosynthesis model in an eastern Indian tropical dry deciduous forest - Shahbaz Ahmad; Arvind Chandra Pandey; Amit Kumar; Nikhil V. Lele; Bimal K. Bhattacharya (Tropical Ecology, 2022)

Neuroprotective and Proneurogenic Effects of Glucosamine in an Internal Carotid Artery Occlusion Model of Ischemia - Priya Jhelum; Mydhili Radhakrishnan; A. R. Sam Paul; Sandeep K. Dey; Avijeet Kamle; Arvind Kumar; Abhay Sharma; Sumana Chakravarty (NeuroMolecular Medicine, 2022)

Performance of pilot-scale constructed wetland osmotic microbial fuel cell under different gravel conditions - Mandar S. Bhagat; Arvind Kumar Mungray; Alka A. Mungray (Environmental Science and Pollution Research, 2022)

Liquefaction hazard assessment in a seismically active region of Himalayas using geotechnical and geophysical investigations: a case study of the Jammu Region - Abdullah Ansari; Falak Zahoor; Kondalamahanaty Seshagiri Rao; Arvind Kumar Jain (Bulletin of Engineering Geology and the Environment, 2022)

Biology and biotechnological aspect of sweet potato (Ipomoea batatas L.): a commercially important tuber crop - Shashikanta Behera; Vijay Bahadur Singh Chauhan; Kalidas Pati; Venkatraman Bansode; Maniyam Nedunchezhiyan; Arvind Kumar Verma; Kumari Monalisa; Pradeep Kumar Naik; Soumendra Kumar Naik (Planta, 2022)

Comparative transcriptomic analysis and antioxidant defense mechanisms in clusterbean (Cyamopsis tetragonoloba (L.) Taub.) genotypes with contrasting drought tolerance - Mohd Akram Ansari; Nasreen Bano; Anil Kumar; Arvind Kumar Dubey; Mehar Hasan Asif; Indraneel Sanyal; Veena Pande; Vivek Pandey (Functional & Integrative Genomics, 2022)

Dielectric studies for rare earth doped magnesium ferrite material - Umesh Chejara; Anamika Prajapati; Arvind Kumar (Environmental Science and Pollution Research, 2022)

Experimental study on piled ring foundation resting on RDFS cushion overlying soft clay - Prince Karandeep Singh; Arvind Kumar (Marine Georesources & Geotechnology, 2022)

Characterization and ecotoxicological risk assessment of sewage sludge from industrial and non-industrial cities - Parul Sundha; Nirmalendu Basak; Arvind Kumar Rai; Priyanka Chandra; Sandeep Bedwal; Gajender Yadav; Rajender Kumar Yadav; Parbodh Chander Sharma (Environmental Science and Pollution Research, 2022)

Endofungal Rhizobium species enhance arsenic tolerance in colonized host plant under arsenic stress - Imran Ahmad; Shiv Narayan; Jagriti Shukla; Pramod Arvind Shirke; Manoj Kumar (Archives of Microbiology, 2022)

PROSAIL and empirical model to evaluate spatio-temporal heterogeneity of canopy chlorophyll content in subtropical forest - Saurabh Kumar Gupta; Arvind Chandra Pandey (Modeling Earth Systems and Environment, 2022)

Long-Term Effect of Alkali and Partially Neutralized Irrigation Water on Soil Quality - Awtar Singh; Arvind Kumar; Rajender Kumar Yadav; Paramjit Singh Minhas; Upasana Saini (Journal of Soil Science and Plant Nutrition, 2022)

Development of near isogenic lines for grain softness through marker assisted backcross breeding in wheat - Tej Pratap Jitendra Kumar; Anjali Rai; Sumit K. Singh; Rajeev Ranjan Kumar; Arvind K. Ahlawat; Savita Saini; R. B. Shukla; Namita Bedi; Anju Mahendru-Singh (Journal of Plant Biochemistry and Biotechnology, 2022)

Assessing the impact of current tropospheric ozone on yield loss and antioxidant defense of six cultivars of rice using ethylenediurea in the lower Gangetic Plains of India - Arvind Kumar Singh; Sabyasachi Mitra; Gouranga Kar (Environmental Science and Pollution Research, 2022)

Management of solid waste marble powder: improving quality of sodium chloride obtained from sulphate-rich lake/subsoil brines with simultaneous recovery of high-purity gypsum and magnesium carbonate hydrate - Rahul J. Sanghavi; Sumesh C. Upadhyay; Arvind Kumar (Environmental Science and Pollution Research, 2022)

Baccaurea ramiflora Lour.: a comprehensive review from traditional usage to pharmacological evidence - Arvind Kumar Goyal; Sushil Kumar Middha; Talambedu Usha (Advances in Traditional Medicine, 2022)

Molecular profiling of BADH2 locus reveals distinct functional allelic polymorphism associated with fragrance variation in Indian aromatic rice germplasm - Gagandeep Singh; S. Gopala Krishnan; Arvind Kumar; K. K. Vinod; Haritha Bollinedi; Ranjith K. Ellur; M. Nagarajan; P. K. Bhowmick; S. M. Madhav; Kuldeep Singh; Ashok K. Singh (Physiology and Molecular Biology of Plants, 2022)

Assessment of snout analysis of Himalayan glaciers: impact studies on Pindari, Kafni, Sundardhunga, and Baljuri base camp glaciers - Arvind Pandey; Deepanshu Parashar; Bidyutjyoti Baruah; Sarita Palni; Arvind Singh Yadav; Ajit Pratap Singh; Pankaj Kumar Bhatt; Charu Pundir (Environmental Monitoring and Assessment, 2022)

An analysis of UK retailers’ initiatives towards circular economy transition and policy-driven directions - Arvind Upadhyay; Anil Kumar; Shaheda Akter (Clean Technologies and Environmental Policy, 2022)

Tropospheric ozone effect on yield, quality and antioxidant defence of six cultivars of jute with ethylene diurea in the lower Gangetic Plains of India - Arvind Kumar Singh; Bijan Majumdar; Gouranga Kar (Arabian Journal of Geosciences, 2022)

Assessing farm-scale spatial variability of soil nutrients in central India for site-specific nutrient management - Sanjib Kumar Behera; Arvind Kumar Shukla; Ashok Kumar Patra; Chandra Prakash; Ajay Tripathi; Suresh Kumar Chaudhari; Ch. Srinivasa Rao (Arabian Journal of Geosciences, 2022)

Radioactivity monitoring in the vicinity of Jawalamukhi thrust NW Himalaya, India for tectonic study - Gulshan Kumar; Reetika Bhadwal; Mukesh Kumar; Punam Kumari; Arvind Kumar; Vivek Walia; Rohit Mehra; Ayush Goyal (Natural Hazards, 2022)

Biological and infestation studies on Araecerus fasciculatus DeGeer a new pest of Melia azadirach L. in India - Arvind Kumar; Aishwarya Ray (International Journal of Tropical Insect Science, 2022)

Investigation of compaction, specific gravity, unconfined compressive strength and cbr of a composite having copper slag and rice husk ash mixed using an alkali activator - Kuldeep Sharma; Arvind Kumar (Innovative Infrastructure Solutions, 2022)

Genome-wide profiling of drought-tolerant Arabidopsis plants over-expressing chickpea MT1 gene reveals transcription factors implicated in stress modulation - Sanoj Kumar; Ankita Yadav; Nasreen Bano; Arvind Kumar Dubey; Rita Verma; Ankesh Pandey; Anil Kumar; Sumit Bag; Sudhakar Srivastava; Indraneel Sanyal (Functional & Integrative Genomics, 2022)

Magnetic adsorbent developed with alkali-thermal pretreated biogas slurry solids for the removal of heavy metals: optimization, kinetic, and equilibrium study - Roshini Sasidharan; Arvind Kumar (Environmental Science and Pollution Research, 2022)

Key drivers of consumption-based carbon emissions: empirical evidence from SAARC countries - Komal Kanwar Shekhawat; Arvind Kumar Yadav; Md Sahnewaz Sanu; Pushp Kumar (Environmental Science and Pollution Research, 2022)

Spatial variability of soil nutrients in apple orchards and agricultural areas in Kinnaur region of cold desert, Trans-Himalaya, India - Praveen Kumar; Pardeep Kumar; Munish Sharma; Arvind Kumar Shukla; Nagender Pal Butail (Environmental Monitoring and Assessment, 2022)

Net ecosystem CO2 exchange from jute crop (Corchorus olitorius L.) and its environmental drivers in tropical Indo-Gangetic plain using open-path eddy covariance technique - Dhananjay Barman; Abhishek Chakraborty; Prabir Kumar Das; Suman Roy; Ritesh Saha; Sonali Paul Mazumdar; Soumya Bandyopadhyay; Arvind Kumar Singh; Sabyasachi Mitra; Dilip Kumar Kundu; Abhishek Bagui; C. S. Murthy; et al. (Environmental Monitoring and Assessment, 2022)

Molecular characterization and genetic diversity studies of Indian soybean (Glycine max (L.) Merr.) cultivars using SSR markers - S. P. Jeevan Kumar; C. Susmita; K. V. Sripathy; Dinesh K. Agarwal; Govind Pal; Arvind Nath Singh; Sanjay Kumar; Abhishek Kumar Rai; Jesus Simal-Gandara (Molecular Biology Reports, 2022)
Background The genetic base of soybean cultivars in India has been reported to be extremely narrow, due to repeated use of few selected and elite genotypes as parents in the breeding programmes. This ultimately led to the reduction of genetic variability among existing soybean cultivars and stagnation in crop yield. Thus in order to enhance production and productivity of soybean, broadening of genetic base and exploring untapped valuable genetic diversity has become quite indispensable. This could be successfully accomplished through molecular characterization of soybean genotypes using various DNA based markers. Hence, an attempt was made to study the molecular divergence and relatedness among 29 genotypes of soybean using SSR markers. Methods and results A total of 35 SSR primers were deployed to study the genetic divergence among 29 genotypes of soybean. Among them, 14 primer pairs were found to be polymorphic producing a total of 34 polymorphic alleles; and the allele number for each locus ranged from two to four with an average of 2.43 alleles per primer pair. Polymorphic information content (PIC) values of SSRs ranged from 0.064 to 0.689 with an average of 0.331. The dendrogram constructed based on dissimilarity indices clustered the 29 genotypes into two major groups and four sub-groups. Similarly, principal coordinate analysis grouped the genotypes into four major groups that exactly corresponded to the clustering of genotypes among four sub-groups of dendrogram. Besides, the study has reported eight unique and two rare alleles that could be potentially utilized for genetic purity analysis and cultivar identification in soybean. Conclusion In the present investigation, two major clusters were reported and grouping of large number of genotypes in each cluster indicated high degree of genetic resemblance and narrow genetic base among the genotypes used in the study. With respect to the primers used in the study, the values of PIC and other related parameters revealed that the selected SSR markers are moderately informative and could be potentially utilized for diversity analysis of soybean. The clustering pattern of dendrogram constructed based on SSR loci profile displayed good agreement with the cultivar’s pedigree information. High level of genetic similarity observed among the genotypes from the present study necessitates the inclusion of wild relatives, land races and traditional cultivars in future soybean breeding programmes to widen the crop gene pool. Thus, hybridization among diverse gene pool could result in more heterotic combinations ultimately enhancing genetic gain, crop yield and resistance to various stress factors.

Spatio-Temporal Variability and Health Risk Assessment of Benzo[a]pyrene in Different Population Through Ambient Air Exposure in Delhi, India - Anchal Garg; N. C. Gupta; Arvind Kumar (Exposure and Health, 2022)

Effect of selected single nucleotide polymorphisms in SLC11A1, ANKRA2, IFNG and PGLYRP1 genes on host susceptibility to Mycobacterium avium subspecies paratuberculosis infection in Indian cattle - B. Gopi; Ran Vir Singh; Satish Kumar; Sushil Kumar; Anuj Chauhan; Arvind Sonwane; Amit Kumar; Jaya Bharati; Shoor Vir Singh (Veterinary Research Communications, 2022)

CAMTA transcription factor enhances salinity and drought tolerance in chickpea (Cicer arietinum L.) - Meenakshi; Anil Kumar; Varun Kumar; Arvind Kumar Dubey; Shiv Narayan; Samir V. Sawant; Veena Pande; Pramod Arvind Shirke; Indraneel Sanyal (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Modelling the effects of ground vibrations on the surface due to blasting in underground coal mines - Shankar Kumar; Bhanwar Singh Choudhary; Arvind Kumar Mishra (Natural Hazards, 2022)

Effect of cadmium and ethylenediamine tetraacetic acid supplementation on cadmium accumulation by roots of Brassica species in Cd spiked soil - Salwinder Singh Dhaliwal; Vivek Sharma; Parminder Kaur Taneja; Arvind Kumar Shukla; Lovedeep Kaur; Gayatri Verma; Vibha Verma; Jagdish Singh (Environmental Science and Pollution Research, 2022)

Livelihood resilience in the face of multiple stressors: biocultural resource-based adaptive strategies among the vulnerable communities - Ranjay K. Singh; Rakesh Bhardwaj; Amish K. Sureja; Arvind Kumar; Anshuman Singh; B. N. Hazarika; S. M. Hussain; Anamika Singh; Y. J. Lego; Orik Rallen (Sustainability Science, 2022)

Novel Co-crystals and Eutectics of Febuxostat: Characterization, Mechanism of Formation, and Improved Dissolution - Moksh Jagia; Dnyaneshwar P. Kale; Arvind Kumar Bansal; Sarsvatkumar Patel (AAPS PharmSciTech, 2021)

Over-expression of chickpea metallothionein 1 gene confers tolerance against major toxic heavy metal stress in Arabidopsis - Arvind Kumar Dubey; Anil Kumar; Navin Kumar; Sanoj Kumar; Meenakshi; Ambedkar Gautam; Mohd Akram Ansari; N. Manika; Swati Lal; Soumit Kumar Behera; Shekhar Mallick; Indraneel Sanyal (Physiology and Molecular Biology of Plants, 2021)

Gene Expression Analysis Identifies Cholesterol Metabolism Dysregulation in Hippocampus of Phenytoin-Resistant Pentylenetetrazol-Kindled Epileptic Mice - Sridhar Amalakanti; Unis Ahmad Bhat; Madhavi B. Mylavarapu; Nitin Khandelwal; N. V. Sundarachary; Sumana Chakravarty; Arvind Kumar (NeuroMolecular Medicine, 2021)

An Efficient Void Aware Framework for Enabling Internet of Underwater Things - Ahmad M. Khasawneh; Maryam Altalhi; Arvind Kumar; Geetika Aggarwal; Omprakash Kaiwartya; Ala’ Khalifeh; Mahmoud Ahmad Al-Khasawneh; Ala Abdulsalam Alarood (Journal of Marine Science and Engineering, 2021)
The Internet of Underwater Things (IoUT) is an emerging area in marine science and engineering. It has witnessed significant research and development attention from both academia and industries due to its growing underwater use cases in oceanographic data collection, pollution monitoring, seismic monitoring, tactical surveillance, and assisted navigation for waterway transport. Information dissemination in the underwater network environment is very critical considering network dynamism, unattainable nodes, and limited resources of the tiny IoUT devices. Existing techniques are majorly based on location-centric beacon messages, which results in higher energy consumption, and wastage of computing resources in tiny IoUT devices. Towards this end, this paper presents an efficient void aware (EVA) framework for information dissemination in IoUT environment. Network architecture is modeled considering potential void region identification in the underwater network environment. An efficient void aware (EVA) information dissemination framework is proposed focusing on detecting void network region, and intelligent void aware data forwarding. The comparative performance evaluation attests to the benefits of the proposed framework in terms of energy consumption, network lifetime, packet delivery ratio, and end-to-end delay for information dissemination in IoUT.

Efficiency and kinetics of Assam crude oil degradation by Pseudomonas aeruginosa and Bacillus sp. - Bobby Chettri; Ningombam A. Singha; Arvind Kumar Singh (Archives of Microbiology, 2021)

Mathematical Models of how the Transpiration Affects Rainfall through Agriculture Crops - Arvind Kumar Misra; Amita Tripathi (Environmental Modeling & Assessment, 2021)

Frequency channeling: a concept to increase the frequency and control the PPV of blast-induced ground vibration waves in multi-hole blast in a surface mine - Chitranjan Prasad Singh; Hemant Agrawal; Arvind Kumar Mishra (Bulletin of Engineering Geology and the Environment, 2021)

Genetic structuring of Drosophila bipectinata in Indian natural populations based on the distribution of cosmopolitan inversions - Gurvachan Singh; Arvind Kumar Singh (Journal of Genetics, 2021)

Risk Assessment of Arsenic Toxicity Through Groundwater-Soil-Rice System in Maldah District, Bengal Delta Basin, India - Rubina Khanam; Gora Chand Hazra; Animesh Ghosh Bag; Pedda Ghouse Peera Sheikh Kulsum; Nitin Chatterjee; Arvind Kumar Shukla (Archives of Environmental Contamination and Toxicology, 2021)

Comparison of Carbon Sequestration Potential of Quercus leucotrichophora–Based Agroforestry Systems and Natural Forest in Central Himalaya, India - Sandeep Kumar; Arvind Bijalwan; Bhupendra Singh; Deepa Rawat; Aalok G. Yewale; Manoj Kumar Riyal; Tarun Kumar Thakur (Water, Air, & Soil Pollution, 2021)

Potential of hyperspectral AVIRIS-NG data for vegetation characterization, species spectral separability, and mapping - Shahbaz Ahmad; Arvind Chandra Pandey; Amit Kumar; Nikhil V. Lele (Applied Geomatics, 2021)

Assessment of near-surface air pollutants at an urban station over the central Indo-Gangetic Basin: Role of pollution transport pathways - Amarendra Singh; Atul Kumar Srivastava; V. Varaprasad; Sunil Kumar; Virendra Pathak; Arvind Kumar Shukla (Meteorology and Atmospheric Physics, 2021)

Spatio-temporal Mapping to Investigate Coral Bleaching in Andaman and Nicobar Islands, India Using Geoinformatics - Md. Wasim; Arvind Chandra Pandey; Amit Kumar; Chandra Shekhar Dwivedi (Journal of the Indian Society of Remote Sensing, 2021)

Increase in summer monsoon rainfall over the northeast India during El Niño years since 1600 - P. Kiran Kumar; Arvind Singh (Climate Dynamics, 2021)

Breaking the mould: understanding the practicality of solar water pumps among small tea planters in a South Asian State of India - Unmilan Kalita; Arup Kumar Hazarika; Arvind Phukan; Dhritiman Kakati; Madhumita Das (Energy, Ecology and Environment, 2021)

Grassroots Approaches for Sustaining Biocultural Diversity and Livelihood Security: Insights from Indian Eastern Himalaya - Ranjay K. Singh; Anshuman Singh; Lobsang Ksherchokpa; Orik Rallen; Bamang Taniang; Yanung J. Lego; Egul Padung; Arvind Kumar; Hui Tag; Volker Mauerhofer (Environmental Management, 2021)

Genomics and breeding innovations for enhancing genetic gain for climate resilience and nutrition traits - Pallavi Sinha; Vikas K. Singh; Abhishek Bohra; Arvind Kumar; Jochen C. Reif; Rajeev K. Varshney (Theoretical and Applied Genetics, 2021)
Key message Integrating genomics technologies and breeding methods to tweak core parameters of the breeder’s equation could accelerate delivery of climate-resilient and nutrient rich crops for future food security. Abstract Accelerating genetic gain in crop improvement programs with respect to climate resilience and nutrition traits, and the realization of the improved gain in farmers’ fields require integration of several approaches. This article focuses on innovative approaches to address core components of the breeder’s equation. A prerequisite to enhancing genetic variance ( σ 2 g ) is the identification or creation of favorable alleles/haplotypes and their deployment for improving key traits. Novel alleles for new and existing target traits need to be accessed and added to the breeding population while maintaining genetic diversity. Selection intensity ( i ) in the breeding program can be improved by testing a larger population size, enabled by the statistical designs with minimal replications and high-throughput phenotyping. Selection priorities and criteria to select appropriate portion of the population too assume an important role. The most important component of breeder′s equation is heritability ( h 2 ). Heritability estimates depend on several factors including the size and the type of population and the statistical methods. The present article starts with a brief discussion on the potential ways to enhance σ 2 g in the population. We highlight statistical methods and experimental designs that could improve trait heritability estimation. We also offer a perspective on reducing the breeding cycle time ( t ), which could be achieved through the selection of appropriate parents, optimizing the breeding scheme, rapid fixation of target alleles, and combining speed breeding with breeding programs to optimize trials for release. Finally, we summarize knowledge from multiple disciplines for enhancing genetic gains for climate resilience and nutritional traits.

Prenatal stress effects on offspring brain and behavior: Mediators, alterations and dysregulated epigenetic mechanisms - Shams Ul Haq; Unis Ahmad Bhat; Arvind Kumar (Journal of Biosciences, 2021)

Spatial Modeling of Some Selected Soil Nutrients Using Geostatistical Approach for Jhandutta Block (Bilaspur District), Himachal Pradesh, India - Praveen Kumar; Pardeep Kumar; Arvind Kumar Shukla (Agricultural Research, 2021)

Chickpea glutaredoxin (CaGrx) gene mitigates drought and salinity stress by modulating the physiological performance and antioxidant defense mechanisms - Anil Kumar; Varun Kumar; Arvind Kumar Dubey; Mohd Akram Ansari; Shiv Narayan; Meenakshi; Sanoj Kumar; Vivek Pandey; Veena Pande; Indraneel Sanyal (Physiology and Molecular Biology of Plants, 2021)

Zinc application enhances yield and alters micronutrients concentration in pigeonpea (Cajanus cajan L. Millsp.) - Sanjib Kumar Behera; Arvind Kumar Shukla; Pooja Singh; Vivek Trivedi; Ashok Kumar Patra; Annangi Subba Rao; Anil Kumar Singh (Nutrient Cycling in Agroecosystems, 2021)

Phytochemical response in rice (Oryza sativa L.) genotype during the vegetative and reproductive stage under drought stress and non-stress conditions - Mahadev Kumbar; Kiran Kamalakar Mirajkar; Kumar Arvind (Journal of Plant Biochemistry and Biotechnology, 2021)

Correction to: Preparation of high-purity magnesium-ammonium-phosphate fertilizer using sea bittern and industrial waste streams - Rahul J. Sanghavi; Rakesh Dobariya; Sameer Bhatti; Arvind Kumar (Environmental Science and Pollution Research, 2021)

Evaluating long-term variability in precipitation and temperature in eastern plateau region, India, and its impact on urban environment - Amit Kumar; Arvind Chandra Pandey; Swati Pandey; P. K. Srivastava (Environment, Development and Sustainability, 2021)

Adaptation to social-ecological stressors: a case study with Indian jujube (Ziziphus mauritiana Lam.) growers of north-western India - Anshuman Singh; Ranjay K. Singh; Arvind Kumar; Ashwani Kumar; Raj Kumar; Neeraj Kumar; Parvender Sheoran; R. K. Yadav; D. K. Sharma (Environment, Development and Sustainability, 2021)

Variability of durum wheat genotypes in terms of physio-biochemical traits against salinity stress - Shobha Soni; Ashwani Kumar; Nirmala Sehrawat; Naresh Kumar; Gurpreet Kaur; Arvind Kumar; Anita Mann (Cereal Research Communications, 2021)

Damage detection of wind turbine system based on signal processing approach: a critical review - Roshan Kumar; Mohamed Ismail; Wei Zhao; Mohammad Noori; Arvind R. Yadav; Shengbo Chen; Vikash Singh; Wael A. Altabey; Ahmad I. H. Silik; Gaurav Kumar; Jayendra Kumar; Arun Balodi (Clean Technologies and Environmental Policy, 2021)

Sugarcane Yield Forecasting Model Based on Weather Parameters - Amit Kumar Verma; Pradeep Kumar Garg; K. S. Hari Prasad; Vinay Kumar Dadhwal; Sunil Kumar Dubey; Arvind Kumar (Sugar Tech, 2021)

Generation of Ophthalmic Nanosuspension of Prednisolone Acetate Using a Novel Technology - Yash Nandwani; Amanpreet Kaur; Arvind Kumar Bansal (Pharmaceutical Research, 2021)

Molecular Basis of Sex Difference in Neuroprotection induced by Hypoxia Preconditioning in Zebrafish - Tapatee Das; Kalyani Soren; Mounica Yerasi; Avijeet Kamle; Arvind Kumar; Sumana Chakravarty (Molecular Neurobiology, 2020)

Use of GRACE time-series data for estimating groundwater storage at small scale - Ch Samurembi Chanu; Harika Munagapati; V M Tiwari; Arvind Kumar; L Elango (Journal of Earth System Science, 2020)

Catalytic peroxidation of acrylic acid from aqueous solution incorporated with highly active La0.5Sr0.5BO3 (B=Cu, Fe and Ni) perovskite-like catalysts - Arvind Kumar; Basheswar Prasad; Krishan Kishor Garg (Journal of Environmental Health Science and Engineering, 2020)

VacPred: Sequence-based prediction of plant vacuole proteins using machine-learning techniques - Arvind Kumar Yadav; Deepak Singla (Journal of Biosciences, 2020)

Utilization of industrial waste—based geopolymers as a soil stabilizer—a review - Kuldeep Sharma; Arvind Kumar (Innovative Infrastructure Solutions, 2020)

Influence of Fly Ash on Geotechnical Behaviour of Red Mud: A Micro-mechanistic Study - Arvind Kumar Jha; Dhanraj Kumar; P. V. Sivapullaiah (Geotechnical and Geological Engineering, 2020)

Conversion of Waste Biomass into Gaseous Fuel: Present Status and Challenges in India - Ravi Kant Bhatia; Govindarajan Ramadoss; Amit Kumar Jain; Rakesh Kumar Dhiman; Shashi Kant Bhatia; Arvind Kumar Bhatt (BioEnergy Research, 2020)

Real-time database for geochemical earthquake precursory research - Arvind Kumar; Vivek Walia; Shih-Jung Lin; Ching-Chou Fu (Natural Hazards, 2020)

Perceived Climate Variability and Compounding Stressors: Implications for Risks to Livelihoods of Smallholder Indian Farmers - Ranjay K. Singh; Anshuman Singh; Satyendra Kumar; Parvender Sheoran; D. K. Sharma; Lindsay C. Stringer; Claire H. Quinn; Arvind Kumar; Dheeraj Singh (Environmental Management, 2020)

Factors affecting properties of MSWI bottom ash employing cement and fiber for geotechnical applications - Davinder Singh; Arvind Kumar (Environment, Development and Sustainability, 2020)

Identification and characterization of Dicer-like genes in leaf rust pathogen (Puccinia triticina) of wheat - Himanshu Dubey; Kanti Kiran; Rajdeep Jaswal; Subhash C. Bhardwaj; Tapan Kumar Mondal; Neha Jain; N. K. Singh; Arvind M. Kayastha; Tilak Raj Sharma (Functional & Integrative Genomics, 2020)

Professor Trevor Platt, FRS, FRSC (1942-2020) – A heartfelt tribute - Aneesh A. Lotliker; Arvind Singh; Nimit Kumar; Rajdeep Roy; Ravidas K. Naik; Satya Prakash (International Journal of Remote Sensing, 2020)

Change detection of landscape connectivity arisen by forest transformation in Hazaribagh wildlife sanctuary, Jharkhand (India) - Saurabh Kumar Gupta; Arvind Chandra Pandey (Spatial Information Research, 2020)

Reduction of blast-induced ground vibration and utilization of explosive energy using low-density explosives for environmentally sensitive areas - Sujit Kumar; Arvind Kumar Mishra (Arabian Journal of Geosciences, 2020)

Blast vibration dependence on total explosives weight in open-pit blasting - Murari Prasad Roy; Arvind Kumar Mishra; Hemant Agrawal; Pradeep Kumar Singh (Arabian Journal of Geosciences, 2020)

A study on influence of blast-induced ground vibration in dragline bench blasting using signature hole analysis - Chitranjan Prasad Singh; Hemant Agrawal; Arvind Kumar Mishra (Arabian Journal of Geosciences, 2020)

In Silico Analysis of New Potent Anti-hyperglycemic Molecule for Diabetes Type 2 Management - Kritika Singh; Praveen Kumar Tripathi; Vinay Kumar Singh; Ashok Kumar Patel; O. N. Srivastava; S. K. Singh; Arvind M. Kayastha (International Journal of Peptide Research and Therapeutics, 2020)

Uncommon non-fermenting Gram-negative bacillary bacteraemia in ICU patients - Sai Saran; Mohan Gurjar; Atul Garg; Chinmoy Sahu; Bhanuprakash Bhaskar; Prabhaker Mishra; Afzal Azim; Banani Poddar; Arvind Kumar Baronia (Infectious Diseases, 2020)

Flood Inundation Mapping and Impact Assessment Using Multi-Temporal Optical and SAR Satellite Data: a Case Study of 2017 Flood in Darbhanga District, Bihar, India - Gaurav Tripathi; Arvind Chandra Pandey; Bikash Ranjan Parida; Amit Kumar (Water Resources Management, 2020)

Understanding the Oral Absorption of Irbesartan Using Biorelevant Dissolution Testing and PBPK Modeling - Navpreet Kaur; Poonam Singh Thakur; Ganesh Shete; Rahul Gangwal; Abhay T. Sangamwar; Arvind Kumar Bansal (AAPS PharmSciTech, 2020)

Preparation of high-purity magnesium-ammonium-phosphate fertilizer using sea bittern and industrial waste streams - Rahul J. Sanghavi; Rakesh Dobariya; Sameer Bhatti; Arvind Kumar (Environmental Science and Pollution Research, 2020)

Forest health estimation in Sholayar Reserve Forest, Kerala using AVIRIS-NG hyperspectral data - Shahbaz Ahmad; Arvind Chandra Pandey; Amit Kumar; Nikhil V. Lele; Bimal K. Bhattacharya (Spatial Information Research, 2020)

Mechanical characteristics of municipal solid waste incineration bottom ash treated with cement and fiber - Davinder Singh; Arvind Kumar (Innovative Infrastructure Solutions, 2019)

Bearing capacity of strip footing resting on fibre-reinforced pond ash overlying soft clay - Sudhir Arora; Arvind Kumar (Innovative Infrastructure Solutions, 2019)

Model tests on geosynthetic-encased construction concrete debris column in fly ash fill - Rajeev Bhatia; Arvind Kumar (Innovative Infrastructure Solutions, 2019)

Studying the behavior of neural models under hybrid and reinforced foundations - Vikas Kumar; Arvind Kumar (Innovative Infrastructure Solutions, 2019)

Thermally induced characterization and modeling of physicochemical, acoustic, rheological, and thermodynamic properties of novel blends of (HEF + AEP) and (HEF + AMP) for CO2/H2S absorption - Sweta Balchandani; Bishnupada Mandal; Swapnil Dharaskar; Arvind Kumar; Syamalendu Bandyopadhyay (Environmental Science and Pollution Research, 2019)

Hydrocarbon degradation potential and competitive persistence of hydrocarbonoclastic bacterium Acinetobacter pittii strain ABC - Bobby Chettri; Ningombam A. Singha; Arghya Mukherjee; Amar Nath Rai; Dhrubajyoti Chattopadhyay; Arvind Kumar Singh (Archives of Microbiology, 2019)

Zinc Application Enhances Superoxide Dismutase and Carbonic Anhydrase Activities in Zinc-Efficient and Zinc-Inefficient Wheat Genotypes - Pooja Singh; Arvind Kumar Shukla; Sanjib Kumar Behera; Pankaj Kumar Tiwari (Journal of Soil Science and Plant Nutrition, 2019)

Combination of UVB Absorbing Titanium Dioxide and Quercetin Nanogel for Skin Cancer Chemoprevention - Arvind Bagde; Ketan Patel; Arindam Mondal; Shallu Kutlehria; Nusrat Chowdhury; Aragaw Gebeyehu; Nilkumar Patel; Nagi Kumar; Mandip Singh (AAPS PharmSciTech, 2019)

Genetic population structure of a highly migratory Hilsa Shad, Tenualosa ilisha, in three river systems, inferred from four mitochondrial genes analysis - Vindhya Mohindra; B. K. Divya; Rajesh Kumar; Rajeev K. Singh; Arvind Kumar Dwivedi; Sangeeta Mandal; Prachi Masih; Kuldeep K. Lal; J. K. Jena (Environmental Biology of Fishes, 2019)

Response of groundwater contamination hazard rating systems to variations in subsoil conditions beneath municipal solid waste (MSW) dumps in developing countries - Amit Kumar; Manoj Datta; B. R. Gurjar; Arvind K. Nema; R. K. Singh (Arabian Journal of Geosciences, 2019)

Assessment of Biopharmaceutical Performance of Supersaturating Formulations of Carbamazepine in Rats Using Physiologically Based Pharmacokinetic Modeling - Samarth D. Thakore; Poonam Singh Thakur; Ganesh Shete; Rahul Gangwal; Ajit S. Narang; Abhay T. Sangamwar; Arvind Kumar Bansal (AAPS PharmSciTech, 2019)

Effect of Crop Management Practices on Crop Growth, Productivity and Profitability of Rice–Wheat System in Western Indo-Gangetic Plains - P. C. Sharma; Ashim Datta; Arvind Kumar Yadav; Madhu Choudhary; H. S. Jat; Andrew McDonald (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Exploring the traits for lodging tolerance in wheat genotypes: a review - Rinki Khobra; Sindhu Sareen; Braj Kishor Meena; Arvind Kumar; Vinod Tiwari; G. P. Singh (Physiology and Molecular Biology of Plants, 2019)

Discovery and profiling of small RNAs from Puccinia triticina by deep sequencing and identification of their potential targets in wheat - Himanshu Dubey; Kanti Kiran; Rajdeep Jaswal; Priyanka Jain; Arvind M Kayastha; Subhash C Bhardwaj; Tapan Kumar Mondal; Tilak Raj Sharma (Functional & Integrative Genomics, 2019)

Evaluating urban growth and its implication on flood hazard and vulnerability in Srinagar city, Kashmir Valley, using geoinformatics - Tauseef Ahmad; Arvind Chandra Pandey; Amit Kumar (Arabian Journal of Geosciences, 2019)

Corrigendum: N2 Fixation in the Eastern Arabian Sea: Probable Role of Heterotrophic Diazotrophs - P. Kiran Kumar; Arvind Singh; R. Ramesh; T. Nallathambi (Frontiers in Marine Science, 2019)

New insights into the catalytic inactivity of mammary gland protein-40, a chitinase-like protein expressed during mammary gland involution - Surender Singh; Suman Choudhary; Vijay Anand; Shalini Jaswal; Arvind K. Verma; Sudarshan Kumar; Jai K. Kaushik; Ashok K. Mohanty (Molecular Biology Reports, 2019)

Comprehensive evaluation of water quality status for entire stretch of Yamuna River, India - Maneesh Jaiswal; Jakir Hussain; Sanjay Kumar Gupta; Mahmoud Nasr; Arvind Kumar Nema (Environmental Monitoring and Assessment, 2019)

Functional annotation of differentially expressed genes under salt stress in Dichanthium annulatum - Anita Mann; Naresh Kumar; Charu Lata; Ashwani Kumar; Arvind Kumar; B. L. Meena (Plant Physiology Reports, 2019)

Isolation and antiproliferative activity of triterpenoids and fatty acids from the leaves and stem of Turraea vogelii Hook. f. ex benth - Abdulmumeen A. Hamid; Olapeju O. Aiyelaagbe; Arvind S. Negi; Fatima Kaneez; Suaib Luqman; Stephen O. Oguntoye; Satish B. Kumar; Marili Zubair (Natural Product Research, 2019)

An experimental study to analyse the behaviour of piled-raft foundation model under the application of vertical load - Vikas Kumar; Arvind Kumar (Innovative Infrastructure Solutions, 2018)

Improved turbidity estimates in complex inland waters using combined NIR–SWIR atmospheric correction approach for Landsat 8 OLI data - Venkata Vijay Arun Kumar Surisetty; Arvind Sahay; Ratheesh Ramakrishnan; Rabindro Nath Samal; Ajay Singh Rajawat (International Journal of Remote Sensing, 2018)

Performance of tire chips–gravel combinations with nonwoven geotextile and encapsulated tire chips layers used as filter/separator under incremental stress levels - M. K. Kaushik; Arvind Kumar; Ajay Bansal (European Journal of Environmental and Civil Engineering, 2018)

Superior adaptation of aerobic rice under drought stress in Iran and validation test of linked SSR markers to major QTLs by MLM analysis across two years - Atefeh Sabouri; Reza Afshari; Tayebeh Raiesi; Haniyeh Babaei Raouf; Elham Nasiri; Masoud Esfahani; Ali Kafi Ghasemi; Arvind Kumar (Molecular Biology Reports, 2018)

Soil gas survey in and around Shanchiao fault of northern Taiwan for establishing continuous monitoring station - Arvind Kumar; Vivek Walia; Yi-Chun Sung; Shih-Jung Lin; Ching-Chou Fu; Kuo-Liang Wen (Acta Geophysica, 2018)

Characterization of some selected mud volcanoes of southern Taiwan - Arvind Kumar; Tsung-Han Yang; Vivek Walia; Yi-Chun Sung; Hasio-Fen Lee; Shih-Jung Lin; Kuo-Liang Wen (Acta Geophysica, 2018)

Cross-Reactivity of Prokaryotic 16S rDNA-Specific Primers to Eukaryotic DNA: Mistaken Microbial Community Profiling in Environmental Samples - Shailendra Yadav; Arvind Kumar; Manish Gupta; S. S. Maitra (Current Microbiology, 2018)

Status of pulse milling processes and technologies: A review - Rajesh Kumar Vishwakarma; Uma Shanker Shivhare; Ram Kishore Gupta; Deep Narayan Yadav; Arvind Jaiswal; Priyanka Prasad (Critical Reviews in Food Science and Nutrition, 2018)

The SbcC and SbcD homologs of the cyanobacterium Anabaena sp. strain PCC7120 (Alr3988 and All4463) contribute independently to DNA repair - Sarita Pandey; Anurag Kirti; Arvind Kumar; Hema Rajaram (Functional & Integrative Genomics, 2018)

Random Forest Tree Based Approach for Blast Design in Surface Mine - Arvind K. Mishra; Silao V. Ramteke; Phalguni Sen; Amit Kumar Verma (Geotechnical and Geological Engineering, 2018)

Evaluation of morpho-physiological traits of MRQ74 pyramided lines with drought yield QTLs - Asmuni Mohd Ikmal; Zainuddin Nurasyikin; Arvind Kumar; Abd Aziz Shamsudin Noraziyah (Euphytica, 2018)

Profiling of Mineral Nutrients and Variability Study in Pumpkin (Cucurbita moschata) Genotypes - Arvind Nagar; Amish Kumar Sureja; Abhijit Kar; Rakesh Bhardwaj; S. Gopala Krishnan; Anilabha Das Munshi (Agricultural Research, 2018)

Influence of Gassing Agent and Density on Detonation Velocity of Bulk Emulsion Explosives - Arvind Kumar Mishra; Manamohan Rout; Deepanshu Ranjan Singh; Sakti Pada Jana (Geotechnical and Geological Engineering, 2018)

Investigation of Need of Natural Bioenhancer for a Metabolism Susceptible Drug—Raloxifene, in a Designed Self-Emulsifying Drug Delivery System - Poonam Singh Thakur; Narinder Singh; Abhay T. Sangamwar; Arvind Kumar Bansal (AAPS PharmSciTech, 2017)

Fitness differences due to allelic variation at Esterase-4 locus in Drosophila ananassae - Kavita Krishnamoorti; Arvind Kumar Singh (Journal of Genetics, 2017)

Effect of Honey on Quality Characteristics of Mutton Spread - Suman Talukder; Sanjod Kumar Mendiratta; Tarun Pal Singh; Ashish Kumar; Rajiv Ranjan Kumar; Arvind Soni (Agricultural Research, 2017)

Depth of soil compaction predominantly affects rice yield reduction by reproductive-stage drought at varietal screening sites in Bangladesh, India, and Nepal - Suresh Prasad Singh; Abhinav Jain; M. S. Anantha; Santosh Tripathi; Subarna Sharma; Santosh Kumar; Archana Prasad; Bhawana Sharma; Biswajit Karmakar; Rudra Bhattarai; Sankar Prasad Das; Shravan K. Singh; et al. (Plant and Soil, 2017)

Marker-assisted breeding to develop the drought-tolerant version of Sabitri, a popular variety from Nepal - Shalabh Dixit; Ram Baran Yadaw; Krishna Kumar Mishra; Arvind Kumar (Euphytica, 2017)
Sabitri is a rice variety grown in a large part of the rainfed areas of Nepal. It was originally developed for irrigated condition; hence, this variety suffers high yield decline under drought. Two QTLs, qDTY 3.2 and qDTY 12.1 , with large effects on grain yield under drought were identified in the Sabitri background in separate QTL mapping studies. The present study reports the development of Sabitri near isogenic lines (NILs) with combinations of these two QTLs and their characterization under drought. To do so, marker-assisted backcross breeding (MABB) was combined with phenotypic selection to develop high-yielding drought-tolerant NILs with Sabitri grain type. Apart from this, drought-tolerant variants for grain type with high yield under non-stress were identified among the developed NILs. Early days to flowering of up to 13 days and reduction in plant height of up to 13 cm as compared to Sabitri were observed in the developed NILs. Some of these NILs showed higher yield compared to Sabitri and relatively higher tolerance to drought, indicating the capture of positive alleles and interactions during the course of selection. The developed NILs possessed high yield potential which make them suitable materials for the testing of water-saving technologies in irrigated areas. Based on their performance, these NILs can be deployed in rainfed areas in Nepal and other countries of South Asia to increase yield stability.

N2 Fixation in the Eastern Arabian Sea: Probable Role of Heterotrophic Diazotrophs - P. Kiran Kumar; Arvind Singh; R. Ramesh; T. Nallathambi (Frontiers in Marine Science, 2017)

Physiological performance of two contrasting rice varieties under water stress - Furqan Khan; Priyanka Upreti; Ruchi Singh; Pradeep Kumar Shukla; Pramod Arvind Shirke (Physiology and Molecular Biology of Plants, 2017)

Expression of chimeric Bt gene, Cry1Aabc in transgenic pigeonpea (cv. Asha) confers resistance to gram pod borer (Helicoverpa armigera Hubner.) - Alok Das; Subhojit Datta; G. K. Sujayanand; Manoj Kumar; Arvind Kumar Singh; Arpan; Alok Shukla; Jamal Ansari; Manoj Kumar; Lubna Faruqui; Shallu Thakur; P. A. Kumar; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Genetic transformation of pigeonpea (Cajanus cajan L.) and screening transgenic progenies based on lateral root inhibition - Alok Das; Manoj Kumar; Arvind Kumar Singh; Arpan; Alok Shukla; Jamal Ansari; Subhojit Datta; Narendra Pratap Singh (Journal of Crop Science and Biotechnology, 2016)

QSAR model development for studying carbonic anhydrase inhibitors as anticonvulsant agents - Ajeet; Arun K. Mishra; Arvind Kumar (Medicinal Chemistry Research, 2016)

Sirtuin 1 and 7 mediate resveratrol-induced recovery from hyper-anxiety in high-fructose-fed prediabetic rats - B Raghunath Reddy; Swati Maitra; Priya Jhelum; K Praveen Kumar; Pankaj K Bagul; Gagandeep Kaur; Sanjay K Banerjee; Arvind Kumar; Sumana Chakravarty (Journal of Biosciences, 2016)

Growth and refinement of excitatory synapses in the human auditory cortex - Arvind Singh Pundir; Utkarsha A. Singh; Nikhil Ahuja; Sonal Makhija; P. C. Dikshit; Bishan Radotra; Praveen Kumar; S. K. Shankar; Anita Mahadevan; T. S. Roy; Soumya Iyengar (Brain Structure and Function, 2016)

An Improved Rating System for Assessing Surface Water Contamination Potential from MSW Landfills - Amit Kumar; Manoj Datta; Arvind K. Nema; R. K. Singh (Environmental Modeling & Assessment, 2016)

Toxicophore exploration as a screening technology for drug design and discovery: techniques, scope and limitations - Pankaj Kumar Singh; Arvind Negi; Pawan Kumar Gupta; Monika Chauhan; Raj Kumar (Archives of Toxicology, 2016)

Gut microbiota of Busseola fusca (Lepidoptera: Noctuidae) - Maxi Snyman; Arvind Kumar Gupta; Cornelius Carlos Bezuidenhout; Sarina Claassens; Johnnie van den Berg (World Journal of Microbiology and Biotechnology, 2016)

EMF radiations (1800 MHz)-inhibited early seedling growth of maize (Zea mays) involves alterations in starch and sucrose metabolism - Arvind Kumar; Harminder Pal Singh; Daizy R. Batish; Shalinder Kaur; Ravinder Kumar Kohli (Protoplasma, 2016)

In silico exploration of cyclooxygenase inhibitory activity of natural compounds found in Myrica nagi using LC-MS - Sushil Kumar Middha; Arvind Kumar Goyal; Ankit Bhardwaj; Raj Kamal; Prakash Lokesh; Hoskote Panditharadhya Prashanth; Gulshan Wadhwa; Talambedu Usha (Symbiosis, 2016)

Evaluation of antioxidative, analgesic and anti-inflammatory activities of methanolic extract of Myrica nagi leaves - an animal model approach - Sushil Kumar Middha; Talambedu Usha; Dinesh Babu; Arvind Kumar Misra; Prakash Lokesh; Arvind Kumar Goyal (Symbiosis, 2016)

Phytometabolomic fingerprinting of selected actinorhizal fruits popularly consumed in North-East India - Pallab Kar; Priyankar Dey; Arvind Kumar Misra; Tapas Kumar Chaudhuri; Arnab Sen (Symbiosis, 2016)

Seismic fragility of base-isolated water storage tanks under non-stationary earthquakes - Sandip Kumar Saha; Vasant A. Matsagar; Arvind K. Jain (Bulletin of Earthquake Engineering, 2016)

An outbreak of encephalitis associated with echovirus 19 in Uttar Pradesh, India, in 2011 - Dharam Veer Singh; Arvind Kumar; Pramesh Kumar; Manjari Baluni; Sneha Ghildiyal; Rashmi Kumar; Usha Kant Misra; Tapan N Dhole (Archives of Virology, 2016)

Micronutrients (Fe, Mn, Zn and Cu) balance under long-term application of fertilizer and manure in a tropical rice-rice system - Mohammad Shahid; Arvind Kumar Shukla; Pratap Bhattacharyya; Rahul Tripathi; Sangita Mohanty; Anjani Kumar; Banwari Lal; Priyanka Gautam; Rajagounder Raja; Bipin Bihari Panda; Brundaban Das; Amaresh Kumar Nayak (Journal of Soils and Sediments, 2016)

NanoCrySP technology for generation of drug nanocrystals: translational aspects and business potential - Ganesh Shete; Arvind Kumar Bansal (Drug Delivery and Translational Research, 2016)

Drainage Performance of Different Sizes Tire Chips used Alone and Mixed with Natural Aggregates as Leachate Drainage Layer Material - M. K. Kaushik; Arvind Kumar; Ajay Bansal (Geotechnical and Geological Engineering, 2016)

Functional characterization of Mammary Gland Protein-40, a chitinase-like glycoprotein expressed during mammary gland apoptosis - Vijay Anand; Shalini Jaswal; Surender Singh; Sudarshan Kumar; Manoj Kumar Jena; Arvind Kumar Verma; Munna Lal Yadav; Jagadeesh Janjanam; Masoud Lotfan; Dhruba Malakar; Ajay Kumar Dang; Tushar Kumar Mohanty; et al. (Apoptosis, 2016)

Metabolomic Analysis Provides Insights on Paraquat-Induced Parkinson-Like Symptoms in Drosophila melanogaster - Arvind Kumar Shukla; Ch. Ratnasekhar; Prakash Pragya; Hitesh Singh Chaouhan; Devendra Kumar Patel; Debapratim Kar Chowdhuri; Mohana Krishna Reddy Mudiam (Molecular Neurobiology, 2016)

Ideal proportion of roughage and concentrate for Malpura ewes to adapt and reproduce in a semi-arid tropical environment - Shekhawat Indu; Veerasamy Sejian; Davendra Kumar; Arvind Pareek; Syed Mohammad Krusheed Naqvi (Tropical Animal Health and Production, 2015)

Site-Specific Nutrient Management under Rice-Based Cropping Systems in Indo-Gangetic Plains: Yield, Profit and Apparent Nutrient Balance - Vinod K. Singh; Arvind K. Shukla; Brahma S. Dwivedi; Mahendra P. Singh; Kaushik Majumdar; Vinod Kumar; Rajendra P. Mishra; Meenu Rani; Susheel K. Singh (Agricultural Research, 2015)

Identifications and removal of diurnal and semidiurnal variations in radon time series data of Hsinhua monitoring station in SW Taiwan using singular spectrum analysis - Arvind Kumar; Vivek Walia; Baldev Raj Arora; Tsanyao Frank Yang; Shih-Jung Lin; Ching-Chou Fu; Cheng-Hong Chen; Kuo-Liang Wen (Natural Hazards, 2015)

Performance Assessment of Gravel–Tire Chips Mixes as Drainage Layer Materials Using Real Active MSW Landfill Leachate - M. K. Kaushik; Arvind Kumar; Ajay Bansal (Geotechnical and Geological Engineering, 2015)

Abiotic Stress Tolerance of Chickpea Genotypes Depends Upon Antioxidative Potential and Nutritional Quality of Seeds - Narinder Kaur; Arvind Kumar; Kamaljit Kaur; Satvir Kaur; Anil K. Gupta; Inderjit Singh (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Status of Available Sulfur in Soils of North-Western Indo-Gangetic Plain and Western Himalayan region and Responses of Rice and Wheat to Applied Sulfur in Farmer’s Fields - Vinod K. Singh; Brahma S. Dwivedi; Arvind K. Shukla; Vinod Kumar; Babooji Gangwar; Meenu Rani; Susheel K. Singh; Rajendra P. Mishra (Agricultural Research, 2015)

Design and synthesis of 4-(4-ethyl-phenyl)-4-oxo-butyric acid (3-oxo-1, 3-diphenyl-propylidene)/[1-(4-chloro-phenyl)-ethylidene]-hydrazide as potential anticonvulsant agents - Vinit Raj; Praveen Kumar; Arvind Kumar (Medicinal Chemistry Research, 2015)

Manganese efficiency in relation to differential production and allocation of carbohydrates between source and sink organs of diverse wheat genotypes - Shalini Jhanji; Upkar Singh Sadana; Arvind Kumar Shukla (Acta Physiologiae Plantarum, 2015)

Real-time PCR carried out on DNA extracted from serum or blood sample is not a good method for surveillance of bovine brucellosis - Arvind Tiwari; Vijai Pal; Prachiti Afley; Deepak Kumar Sharma; Chandra Shekhar Bhatnagar; Bhupendra Bhardwaj; Ganga Prasad Rai; Subodh Kumar (Tropical Animal Health and Production, 2014)

Prevalence of Pathological Conditions in Zoo/Wild Animals in India: A Retrospective Study Based on Necropsy - Anil Kumar Sharma; Shivasharanappa Nayakwadi; Gauri Arvind Chandratre; Mohini Saini; Asit Das; Sachin Shaligram Raut; Devendra Swarup; Ramesh Somvanshi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Pattern of Phenotypic Variation Among Three Populations of Indian Major Carp, Catla catla (Hamilton, 1822) Using Truss Network System in the Ganga Basin, India - Uttam Kumar Sarkar; Javaid Iqbal Mir; Arvind Kumar Dwivedi; Amar Pal; Joykrushna Jena (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

H2O2 pretreated rice seedlings specifically reduces arsenate not arsenite: difference in nutrient uptake and antioxidant defense response in a contrasting pair of rice cultivars - Shekhar Mallick; Navin Kumar; Sarita Sinha; Arvind Kumar Dubey; Rudra Deo Tripathi; Vivek Srivastav (Physiology and Molecular Biology of Plants, 2014)

Erratum to: Impact of correlated inputs to neurons: modeling observations from in vivo intracellular recordings - Man Yi Yim; Arvind Kumar; Ad Aertsen; Stefan Rotter (Journal of Computational Neuroscience, 2014)

Impact of correlated inputs to neurons: modeling observations from in vivo intracellular recordings - Man Yi Yim; Arvind Kumar; Ad Aertsen; Stefan Rotter (Journal of Computational Neuroscience, 2014)

Gypsum Induced Strength Behaviour of Fly Ash-Lime Stabilized Expansive Soil - P. V. Sivapullaiah; Arvind Kumar Jha (Geotechnical and Geological Engineering, 2014)

The lace bug Cochlochila bullita (Stål), a destructive pest of Ocimum sanctum in Jharkhand, India - Arvind Kumar (Phytoparasitica, 2014)

Polymorphism of cytokine and innate immunity genes associated with bovine brucellosis in cattle - Om Prakash; Amit Kumar; Arvind Sonwane; Rajesh Rathore; Ran Vir Singh; Anuj Chauhan; Pushpendra Kumar; R. Renjith; Ramji Yadav; Ashish Bhaladhare; Mohd Baqir; Deepak Sharma (Molecular Biology Reports, 2014)

Comparative Pattern of Reproductive Traits in Labeo rohita (Hamilton 1822) from Six Tropical Rivers of Ganges Basin: A New Insight - Javaid Iqbal Mir; Uttam Kumar Sarkar; Arvind Kumar Dwivedi; Om Prakash Gusain; Joykrushna Jena (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Bearing Capacity of Eccentrically–Obliquely Loaded Footings Resting on Fiber-Reinforced Sand - Arshdeep Kaur; Arvind Kumar (Geotechnical and Geological Engineering, 2014)

Antineoplastic and immunomodulatory effect of polyphenolic components of Achyranthes aspera (PCA) extract on urethane induced lung cancer in vivo - Chandradeo Narayan; Arvind Kumar (Molecular Biology Reports, 2014)

Characterization of polymorphic microsatellite markers and genetic diversity in wild bronze featherback, Notopterus notopterus (Pallas, 1769) - Arti Gupta; Kuldeep K. Lal; Peyush Punia; Rajeev K. Singh; Vindhya Mohindra; Rama S. Sah; Rajesh Kumar; Rupesh K. Luhariya; Arvind K. Dwivedi; Prachi Masih; R. M. Mishra; J. K. Jena (Molecular Biology Reports, 2013)

Synthesis and SAR investigation of natural phenylpropene-derived methoxylated cinnamaldehydes and their novel Schiff bases as potent antimicrobial and antioxidant agents - Upendra K. Sharma; Swati Sood; Nandini Sharma; Praveen Rahi; Rakesh Kumar; Arun K. Sinha; Arvind Gulati (Medicinal Chemistry Research, 2013)

In silico–based combinatorial pharmacophore modelling and docking studies of GSK-3β and GK inhibitors of Hippophae - Sushil Kumar Middha; Arvind Kumar Goyal; Syed Ahmed Faizan; Nethramurthy Sanghamitra; Bharat Chandra Basistha; Talambedu Usha (Journal of Biosciences, 2013)

Soil gas radon–thoron monitoring in Dharamsala area of north-west Himalayas, India using solid state nuclear track detectors - GULSHAN KUMAR; ARVIND KUMAR; VIVEK WALIA; JITENDER KUMAR; VIKASH GUPTA; TSANYAO FRANK YANG; SURINDER SINGH; BIKRAMJIT SINGH BAJWA (Journal of Earth System Science, 2013)

In vitro cytotoxicity, antimicrobial, and metal-chelating activity of triterpene saponins from tea seed grown in Kangra valley, India - Robin Joshi; Swati Sood; Poonam Dogra; Madhvi Mahendru; Dharmesh Kumar; Shalika Bhangalia; Harish Chandra Pal; Neeraj Kumar; Shashi Bhushan; Arvind Gulati; Ajit Kumar Saxena; Ashu Gulati (Medicinal Chemistry Research, 2013)

Radon-thoron monitoring in Tatun volcanic areas of northern Taiwan using LR-115 alpha track detector technique: Pre-calibration and installation - Arvind Kumar; Vivek Walia; Tsanyao Frank Yang; Hsiao-Hsien Chang; Shih-Jung Lin; Karumpil Philips Eappen; Baldev Raj Arora (Acta Geophysica, 2013)

Effect of Counterion on the Solid State Photodegradation Behavior of Prazosin Salts - Lokesh Kumar; Rajan Jog; Saranjit Singh; Arvind Bansal (AAPS PharmSciTech, 2013)

Auxin transport inhibitor induced low complexity petiolated leaves and sessile leaf-like stipules and architectures of heritable leaf and stipule mutants in Pisum sativum suggest that its simple lobed stipules and compound leaf represent ancestral forms in angiosperms - ARVIND KUMAR KUMAR; VISHAKHA SHARMA; MOINUDDIN KHAN; MALI RAM HINDALA; SUSHIL KUMAR (Journal of Genetics, 2013)

Urban Built-up Area Assessment of Ranchi Township Using Cartosat-I Stereopairs Satellite Images - Arvind Chandra Pandey; Amit Kumar; A. T. Jeyaseelan (Journal of the Indian Society of Remote Sensing, 2013)

Molecular identification and phylogenetic study of coxsackievirus A24 variant isolated from an outbreak of acute hemorrhagic conjunctivitis in India in 2010 - Deepti Shukla; Arvind Kumar; Shalini Srivastava; Tapan N. Dhole (Archives of Virology, 2013)

Effect of Counterions on Physicochemical Properties of Prazosin Salts - Lokesh Kumar; Chhuttan Lal Meena; Yogesh B. Pawar; Banrida Wahlang; Kulbhushan Tikoo; Rahul Jain; Arvind K. Bansal (AAPS PharmSciTech, 2013)

Pisum sativum wild-type and mutant stipules and those induced by an auxin transport inhibitor demonstrate the entire diversity of laminated stipules observed in angiosperms - Arvind Kumar; Vishakha Sharma; Moinuddin Khan; Bhumi Nath Tripathi; Sushil Kumar (Protoplasma, 2013)

Molecular identification of enteroviruses associated with aseptic meningitis in children from India - Arvind Kumar; Deepti Shukla; Rashmi Kumar; Mohammad Z. Idris; Prashant Jauhari; Shalini Srivastava; Tapan N. Dhole (Archives of Virology, 2013)

Antidiabetic effect of Eclipta alba associated with the inhibition of alpha-glucosidase and aldose reductase - Natasha Jaiswal; Vikram Bhatia; Swayam Prakash Srivastava; Arvind Kumar Srivastava; Akhilesh Kumar Tamrakar (Natural Product Research, 2012)

COCHLEATA controls leaf size and secondary inflorescence architecture via negative regulation of UNIFOLIATA (LEAFY ortholog) gene in garden pea Pisum sativum - Vishakha Sharma; Swati Chaudhary; Arvind Kumar; Sushil Kumar (Journal of Biosciences, 2012)

Genetic interaction and mapping studies on the leaflet development (lld) mutant in Pisum sativum - SUSHIL KUMAR; RAGHVENDRA KUMAR MISHRA; ARVIND KUMAR; SWATI CHAUDHARY; VISHAKHA SHARMA; RENU KUMARI (Journal of Genetics, 2012)

Development of Improved Horticultural Genotypes Characterized by Novel Over-Flowering Inflorescence Trait in Periwinkle Catharanthus roseus - Sushil Kumar; Swati Chaudhary; Renu Kumari; Vishakha Sharma; Arvind Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2012)

Homology modeling, molecular dynamics and inhibitor binding study on MurD ligase of Mycobacterium tuberculosis - Akanksha Arvind; Vivek Kumar; Parameswaran Saravanan; C. Gopi Mohan (Interdisciplinary Sciences: Computational Life Sciences, 2012)

Correlation of partial env gene sequences with disease progression parameters in HIV-positive pregnant women from India - Supriya Singh; Shashi Khare; Sudha Prasad; R. L. Ichhpujani; S. S. Negi; Sachin Kumar; D. S. Rawat; L. S. Chauhan; Arvind Rai (Medical Microbiology and Immunology, 2012)

Characterization of free-living cyanobacterial strains and their competence to colonize rice roots - Chingkheihunba Akoijam; Arvind Kumar Singh; Amar Nath Rai (Biology and Fertility of Soils, 2012)

Fine mapping of QTLs for rice grain yield under drought reveals sub-QTLs conferring a response to variable drought severities - Shalabh Dixit; B. P. Mallikarjuna Swamy; Prashant Vikram; H. U. Ahmed; M. T. Sta Cruz; Modesto Amante; Dinesh Atri; Hei Leung; Arvind Kumar (Theoretical and Applied Genetics, 2012)

Comprehensive gene expression analysis of the NAC gene family under normal growth conditions, hormone treatment, and drought stress conditions in rice using near-isogenic lines (NILs) generated from crossing Aday Selection (drought tolerant) and IR64 - Mohammed Nuruzzaman; Akhter Most Sharoni; Kouji Satoh; Ali Moumeni; Ramiah Venuprasad; Rachid Serraj; Arvind Kumar; Hei Leung; Kotb Attia; Shoshi Kikuchi (Molecular Genetics and Genomics, 2012)

Microbial Biomass and Carbon Mineralization in Agricultural Soils as Affected by Pesticide Addition - Anjani Kumar; A. K. Nayak; Arvind K. Shukla; B. B. Panda; R. Raja; Mohammad Shahid; Rahul Tripathi; Sangita Mohanty; P. C. Rath (Bulletin of Environmental Contamination and Toxicology, 2012)

Expression of medium and heavy chain neurofilaments in the developing human auditory cortex - Arvind Singh Pundir; L. Shahul Hameed; P. C. Dikshit; Praveen Kumar; Surender Mohan; Bishan Radotra; S. K. Shankar; Anita Mahadevan; Soumya Iyengar (Brain Structure and Function, 2012)

P2X7 Receptor–Pannexin 1 Hemichannel Association: Effect of Extracellular Calcium on Membrane Permeabilization - V. Poornima; M. Madhupriya; S. Kootar; G. Sujatha; Arvind Kumar; Amal Kanti Bera (Journal of Molecular Neuroscience, 2012)

Mercury bioremediation by mercury accumulating Enterobacter sp. cells and its alginate immobilized application - Arvind Sinha; Sunil Kumar Khare (Biodegradation, 2012)

Comparative transcriptome analysis of AP2/EREBP gene family under normal and hormone treatments, and under two drought stresses in NILs setup by Aday Selection and IR64 - Akhter Most Sharoni; Mohammed Nuruzzaman; Kouji Satoh; Ali Moumeni; Kotb Attia; Ramiah Venuprasad; Rachid Serraj; Arvind Kumar; Hei Leung; A. K. M. Rafiul Islam; Shoshi Kikuchi (Molecular Genetics and Genomics, 2012)

In situ measurements of radon levels in water and soil and exhalation rate in areas of Malwa belt of Punjab (India) - Sanjeev Kumar; Surinder Singh; Bikramjit S. Bajwa; Arvind D. Sabharwal (Isotopes in Environmental and Health Studies, 2011)

Antidiabetic and antidyslipidemic activities of Cuminum cyminum L. in validated animal models - Rohit Srivsatava; Swayam Prakash Srivastava; Natasha Jaiswal; Akansha Mishra; Rakesh Maurya; Arvind Kumar Srivastava (Medicinal Chemistry Research, 2011)

Evaluation of urban sprawl pattern in the tribal-dominated cities of Jharkhand state, India - Amit Kumar; Arvind Chandra Pandey; Najmul Hoda; A. T. Jeyaseelan (International Journal of Remote Sensing, 2011)

Molecular typing and distribution of filamentous heterocystous cyanobacteria isolated from two distinctly located regions in North-Eastern India - Chingkheihunba Akoijam; Arvind Kumar Singh (World Journal of Microbiology and Biotechnology, 2011)

Comparative oral bioavailability advantage from curcumin formulations - Bhushan Munjal; Yogesh Bapurao Pawar; Sarsvatkumar Babulal Patel; Arvind Kumar Bansal (Drug Delivery and Translational Research, 2011)

Evaluating the Long-term Urban Expansion of Ranchi Urban Agglomeration, India Using Geospatial Technology - Amit Kumar; Arvind Chandra Pandey; Najmul Hoda; A. T. Jeyaseelan (Journal of the Indian Society of Remote Sensing, 2011)

Freeze–thaw induced genotoxicity in buffalo (Bubalus bubalis) spermatozoa in relation to total antioxidant status - Raj Kumar; G. Jagan Mohanarao; Arvind; S. K. Atreja (Molecular Biology Reports, 2011)

Soil gas radon analysis in some areas of Northern Punjab, India - Bhupinder Singh; Surinder Singh; Bikramjit Singh Bajwa; Joga Singh; Arvind Kumar (Environmental Monitoring and Assessment, 2011)

Dormancy and Flowering Are Regulated by the Reciprocal Interaction Between Cytokinin and Gibberellin in Zantedeschia - Arvind Kumar Subbaraj; Keith Allen Funnell; David John Woolley (Journal of Plant Growth Regulation, 2010)

A Time-Dependent System for Evaluating Groundwater Contamination Hazard Rating of Municipal Solid Waste Dumps - Raj Kumar Singh; Manoj Datta; Arvind Kumar Nema (Environmental Modeling & Assessment, 2010)

Performance of Scrap Tire Shreds as a Potential Leachate Collection Medium - Gunjan Bhalla; Arvind Kumar; Ajay Bansal (Geotechnical and Geological Engineering, 2010)

Genetic control of leaf-blade morphogenesis by the INSECATUS gene in Pisum sativum - Sushil Kumar; Swati Chaudhary; Vishakha Sharma; Renu Kumari; Raghvendra Kumar Mishra; Arvind Kumar; Debjani Roy Choudhury; Ruchi Jha; Anupama Priyadarshini; Arun Kumar (Journal of Genetics, 2010)

Solid State Characterization of Commercial Crystalline and Amorphous Atorvastatin Calcium Samples - Ganesh Shete; Vibha Puri; Lokesh Kumar; Arvind K. Bansal (AAPS PharmSciTech, 2010)

Inhibition of 1,2-dimethylhydrazine induced colon genotoxicity in rats by the administration of probiotic curd - Arvind Kumar; Nikhlesh Kumar Singh; Pushpalata Rabindra Sinha (Molecular Biology Reports, 2010)

Effect of mineral phosphates on growth and nitrogen fixation of diazotrophic cyanobacteria Anabaena variabilis and Westiellopsis prolifica - Mahesh S. Yandigeri; Arvind K. Yadav; Kamlesh Kumar Meena; Sunil Pabbi (Antonie van Leeuwenhoek, 2010)

Antihyperglycaemic effect of an unusual amino acid (4-hydroxyisoleucine) in C57BL/KsJ-db/db mice - A.B. Singh; A.K. Tamarkar; Shweta; T. Narender; Arvind Kumar Srivastava (Natural Product Research, 2010)

Intervention of Acidophilus-casei dahi and Wheat bran against molecular alteration in colon carcinogenesis - Arvind Kumar; Nikhlesh Kumar Singh; Pushpalata Rabindra Sinha; Raj Kumar (Molecular Biology Reports, 2010)

Guanidine hydrochloride and urea-induced unfolding of Brugia malayi hexokinase - Alok Ranjan Singh; Shweta Joshi; Rahul Arya; Arvind Mohan Kayastha; Jitendra Kumar Saxena (European Biophysics Journal, 2010)

Antidyslipidaemic activity of Glycyrrhiza glabra in high fructose diet induced dsyslipidaemic Syrian golden hamsters - Santosh Kumar Maurya; Kanwal Raj; Arvind Kumar Srivastava (Indian Journal of Clinical Biochemistry, 2009)

Genetic Assessment of Traits and Genetic Relationship in Blackgram (Vigna mungo) Revealed by Isoenzymes - Ajay Kumar Singh; Avinash Mishra; Arvind Shukla (Biochemical Genetics, 2009)

Structure and activities of a steroidal saponin from Chlorophytum nimonii (Grah) Dalz - Vijai Lakshmi; Rajesh Kumar; Kartikey Pandey; Bhawani Shanker Joshi; Raja Roy; Kunnath Padamnabham Madhusudanan; Priti Tiwari; Arvind Kumar Srivastava (Natural Product Research, 2009)

Phylogenetic profiling of bacterial community from two intimately located sites in Balramgari, North-East coast of India - Arvind Kumar Gupta; Ashraf Yusuf Rangrez; Pankaj Verma; Anil Chatterji; Yogesh S. Shouche (Indian Journal of Microbiology, 2009)

Molecular diversity of Frankia from root nodules of Hippophae salicifolia D.Don found in Sikkim - Anindita Khan; David D. Myrold; Arvind Kumar Misra (Indian Journal of Microbiology, 2009)

Characterization of the effect of a QTL for drought resistance in rice, qtl12.1, over a range of environments in the Philippines and eastern India - Jérôme Bernier; Arvind Kumar; Ramaiah Venuprasad; Dean Spaner; Satish Verulkar; Nimai P. Mandal; Pramod K. Sinha; Puvvada Peeraju; Praba R. Dongre; R. N. Mahto; Gary Atlin (Euphytica, 2009)

Color removal from paper mill effluent through adsorption technology - C. K. Jain; Arvind Kumar; M. Hayssam Izazy (Environmental Monitoring and Assessment, 2009)

Novel class of hybrid natural products as antidiabetic agents - Kanwal Raj; Namita Misra; Geetali Pachauri; Mithelesh Sharma; Akhilesh Kumar Tamrakar; Amar Bahadur Singh; Arvind Kumar Srivastava; K. Phani Kiran; C.V. Narasimha Rao; S.R. Prubhu (Natural Product Research, 2009)

Geoacoustic inversion using adaptive neuro-fuzzy inference system - Satyanarayana Yegireddi; Arvind Kumar (Computational Geosciences, 2008)

Synthesis of 3,5-disubstituted isoxazolines as protein tyrosine phosphatase 1B inhibitors - Rakesh Maurya; Prasoon Gupta; Ghufran Ahmad; Dinesh Kumar Yadav; Kailash Chand; Amar Bahadur Singh; Akhilesh K. Tamrakar; Arvind K. Srivastava (Medicinal Chemistry Research, 2008)

Antihyperglycaemic activity of Sinularia firma and Sinularia erecta in streptozotocin-induced diabetic rats - Akhilesh Kumar Tamrakar; Priti Tiwari; Rehan Ahmad; Rajesh Kumar; Vijai Lakshmi; Mahendra Nath Srivastava; Arvind Kumar Srivastava (Medicinal Chemistry Research, 2008)

Antihyperglycaemic activity of Ceriops tagal in normoglycaemic and streptozotocin-induced diabetic rats - Priti Tiwari; Akhilesh Kumar Tamrakar; Rehan Ahmad; Mahendra Nath Srivastava; Rajesh Kumar; Vijai Lakshmi; Arvind Kumar Srivastava (Medicinal Chemistry Research, 2008)

Stimulatory effect of Ceriops tagal on hexose uptake in L6 muscle cells in culture - Akhilesh Kumar Tamrakar; Rajesh Kumar; Ramesh Sharma; Anil Kumar Balapure; Vijai Lakshmi; Arvind Kumar Srivastava (Natural Product Research, 2008)

A Common Transport System for Methionine, l-methionine-dl-Sulfoximine (MSX), and Phosphinothricin (PPT) in the Diazotrophic Cyanobacterium Nostoc muscorum - Arvind Kumar Singh; Mayashree B. Syiem; Rajkumar S. Singh; Samrat Adhikari; Amar Nath Rai (Current Microbiology, 2008)

Assessment of reproductive potential of different populations of Angelica glauca Edgew., a critically endangered Himalayan Medicinal Herb - Anil Kumar Bisht; Arvind Bhatt; R. S. Rawal; Uppeandra Dhar (Journal of Mountain Science, 2008)

Lubrication potential of magnesium stearate studied on instrumented rotary tablet press - Sarsvatkumar Patel; Aditya Mohan Kaushal; Arvind Kumar Bansal (AAPS PharmSciTech, 2007)

Uranium, Radium and Radon Measurements in the Environs of Nurpur Area, Himachal Himalayas, India - Surinder Singh; Dinesh Kumar Sharma; Sunil Dhar; Arvind Kumar; Ajay Kumar (Environmental Monitoring and Assessment, 2007)

Analysis of square and rectangular footings subjected to eccentric-inclined load resting on reinforced sand - Swami Saran; Surendra Kumar; K.G. Garg; Arvind Kumar (Geotechnical and Geological Engineering, 2007)

Effect of Particle Size and Compression Force on Compaction Behavior and Derived Mathematical Parameters of Compressibility - Sarsvatkumar Patel; Aditya Mohan Kaushal; Arvind Kumar Bansal (Pharmaceutical Research, 2007)

Bearing capacity of square footings on reinforced layered soil - Arvind Kumar; B. S. Walia (Geotechnical and Geological Engineering, 2006)

Pressure–settlement characteristics of rectangular footings on reinforced sand - Arvind Kumar; Baljit Singh Walia; Swami Saran (Geotechnical and Geological Engineering, 2005)

Prevalence of insulin resistance in first degree relatives of type-2 diabetes mellitus patients: A prospective study in north Indian population - Arvind Kumar; Poornima Tewari; Sibasis S. Sahoo; Arvind Kumar Srivastava (Indian Journal of Clinical Biochemistry, 2005)

Anthropogenic disturbances and plant biodiversity in forests of Uttaranchal, central Himalaya - Arvind Kumar; Jeet Ram (Biodiversity and Conservation, 2005)

Closely spaced rectangular footings on reinforced sand - Arvind Kumar; Swami Saran (Geotechnical and Geological Engineering, 2004)

Stability and Solubility of Celecoxib-PVP Amorphous Dispersions: A Molecular Perspective - Piyush Gupta; Vasu Kumar Kakumanu; Arvind K. Bansal (Pharmaceutical Research, 2004)

Sequence analysis of the long arm of rice chromosome 11 for rice?wheat synteny - Saurabh Raghuvanshi; Subodh K. Srivastava; Anupama Gaur; Ajit K. Pal; Vivek Dalal; Archana Singh; Irfan A. Ghazi; Ashutosh Bhargav; Mahavir Yadav; Anupam Dixit; Kamlesh Batra; Kishor Gaikwad; et al. (Functional & Integrative Genomics, 2004)

Bearing capacity of rectangular footing on reinforced soil - Arvind Kumar; Swami Saran (Geotechnical and Geological Engineering, 2003)

Evolutionary implications of nucleotide sequence relatedness between Alnus nepalensis and Alnus glutinosa and also between corresponding Frankia microsymbionts - Rajani Varghese; Vineeta Singh Chauhan; Arvind Kumar Misra (Plant and Soil, 2003)

A new gene for resistance in rice to Asian rice gall midge (Orseolia oryzae Wood Mason) biotype 1 population at Raipur, India - M. N. Shrivastava; Arvind Kumar; Sandeep Bhandarkar; B. C. Shukla; K. C. Agrawal (Euphytica, 2003)

Enthalpy Relaxation Studies of Celecoxib Amorphous Mixtures - Vasu Kumar Kakumanu; Arvind K. Bansal (Pharmaceutical Research, 2002)

Isolation and Characterization of a Chlorate-Resistant Mutant (Clo- R ) of the Symbiotic Cyanobacterium Nostoc ANTH: Heterocyst Formation and N 2 -Fixation in the Presence of Nitrate, and Evidence for Separate Nitrate and Nitrite Transport Systems - Jyotirmoy Bhattacharya; Arvind Kumar Singh; Amar Nath Rai (Current Microbiology, 2002)

Antialgal activity of a hepatotoxin-producing cyanobacterium, Microcystis aeruginosa - Dhananjaya P. Singh; M.B. Tyagi; Arvind Kumar; J.K. Thakur; Ashok Kumar (World Journal of Microbiology and Biotechnology, 2001)

Hierarchical Perception of Stimuli During Case Construction in the Bagworm Moth Eumeta crameri (Lepidoptera: Psychidae) - Atanu Kumar Pati; Arvind Agrawal (Journal of Insect Behavior, 2000)

Exogenous Cytokinin Application Increases Cell Membrane and Chlorophyll Stability in Wheat (Triticum aestivum L.) - N. K. Gupta; Sunita Gupta; Arvind Kumar (Cereal Research Communications, 2000)

Sex Ratio of Campoletis Chlorideae Uchida in Response to Helicoverpa Armigera (Hübner) Density - Nikhil Kumar; Arvind Kumar; C. P. M. Tripathi (International Journal of Tropical Insect Science, 2000)

Short communication: Bacillus cereus capable of degrading SDS shows growth with a variety of detergents - Kusum Lata Singh; Arvind Kumar; Ashok Kumar (World Journal of Microbiology and Biotechnology, 1998)

Cooling age record of domal uplift in the core of the Higher Himalayan Crystallines (HHC), southwest Zanskar, India - Rasoul B. Sorkhabi; Arvind K. Jain; Tetsumaru Itaya; Shiro Fukui; Nand Lal; Ashok Kumar (Journal of Earth System Science, 1997)

Parasitoid-host relationship betweenTrioxys (Binodoxys) Indicus [Hymenoptera: Aphidiidae] andAphis Craccivora [Hemiptera: Aphididae]. VI. Impact of males on the number of progeny of the parasitoid reared on certain host plants - Arvind Kumar; S. Shanker; K. P. Pandey; T. B. Sinha; C. P. M. Tripathi (BioControl, 1988)